Correction to: Diacerein improves liver fibrosis, steatosis, and atherosclerosis in ApoE knockout mice - Jie-Eun Lee; Isom Jin; Jung-Jae Lee; Jisu Jung; Jee-In Lee; Bo-Rahm Kim; Tae Jung Oh; Yun Kyung Lee; Sung Hee Choi (Journal of Molecular Medicine, 2026)

Diacerein improves liver fibrosis, steatosis, and atherosclerosis in ApoE knockout mice - Jie-Eun Lee; Isom Jin; Jung-Jae Lee; Jisu Jung; Jee-In Lee; Bo-Rahm Kim; Tae Jung Oh; Yun Kyung Lee; Sung Hee Choi (Journal of Molecular Medicine, 2026)
Non-alcoholic fatty liver disease and atherosclerosis may share a common pathogenesis involving chronic IL-1β-induced inflammation. We aimed to evaluate the efficacy of diacerein, an IL-1 pathway inhibitor, in improving liver fibrosis, steatosis, and atherosclerosis in apolipoprotein E-knockout (apoE k/o) mice. ApoE k/o mice fed a high-fat diet (HFD) were divided into three groups based on diacerein dosage. Liver fat accumulation and fibrosis severity were compared across groups, along with changes in the expression of genes related to lipid metabolism and fibrosis. Atherosclerotic burden in the aorta was evaluated via en face analysis, and the related signaling pathway was verified in vitro. Diacerein treatment reduced the amount of collagen fibers and fat accumulation in the liver in a dose-dependent manner as well as fibrosis-related gene expression. Atherosclerotic plaque burden in the aorta showed a decreasing trend with diacerein treatment, accompanied by reduced expression of pro-inflammatory cytokines, including TNF-α. Diacerein treatment ameliorated liver steatosis/fibrosis and showed beneficial effects on atherosclerosis-related mechanisms in HFD-fed apoE k/o mice. Given its dual anti-inflammatory and anti-fibrotic actions, diacerein represents a promising therapeutic candidate for metabolic disorders characterized by chronic inflammation. Key messages We analyzed the effects of diacerein on liver fibrosis, steatosis, and atherosclerosis in apolipoprotein E knockout (apoE k/o) mice. Diacerein reduced fat accumulation in the liver and collagen fibers in the liver. It decreased the expression of genes related to fibrosis and the burden of atherosclerotic plaque in the aorta. The expression of pro-inflammatory cytokines was reduced. Treatment of apoE knockout mice fed an HFD with diacerein effectively ameliorated liver steatosis/fibrosis and atherosclerosis. Graphical Abstract

Low muscle mass, obesity, and cause-specific mortality in cancer patients: a nationwide cohort study - Dagyeong Lee; Bongseong Kim; Kyu-won Jung; Ga Eun Nam; Sang Youl Rhee; Seonghye Kim; Sohyun Chun; In Young Cho; Kyungdo Han; Dong Wook Shin (Cancer Causes & Control, 2026)

Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

Synergistic multiscale structural engineering of hollow carbon spheres and 3D folded architectures for interfacial solar steam generation - Jyoti K; Dowon Moon; Jinsil Kim; Hamin Lee; Yunha Jung; Hyun Soo Han; Tatachari Santhanagopalan Shridharan; Jin-Sung Park; In Sun Cho (Chemical Engineering Journal, 2026)

Development of Korea Air quality observation-based Box model (KAB) - Haeju Lee; Na-Hyeon Kim; Seonghui Lim; Minjoong J. Kim; Minseung Yeo; Min Young Kim; Taehyeon Kim; Ho-Jin Lim; Chang Hoon Jung; Ji Yi Lee; In Ho Song; Gookyoung Heo; et al. (Atmospheric Environment, 2026)

Lactococcus Lactis Subsp. Lactis CAB701 Reduces Body fat mass in Adults with Overweight or Obesity: A Randomized, Double-Blind, Placebo-Controlled Trial - Jung in Choi; Ye Li Lee; Sang Yeoup Lee (Probiotics and Antimicrobial Proteins, 2026)
Probiotic-based strategies have gained increasing attention as potential interventions for obesity and metabolic disorders. Lactococcus lactis subsp. lactis CAB701 (CAB701), a cabbage-derived probiotic strain, has demonstrated anti-adipogenic activity in preclinical studies; however, its clinical efficacy has not been established. We conducted a single-centre, randomized, double-blind, placebo-controlled 12-week trial in 100 Korean adults with overweight or obesity (mean age 48.9 ± 13.9 years; body mass index (BMI) 25.8 ± 1.8 kg/m²; 19% men). Participants were randomized 1:1 to receive 150 mg/day CAB701 or placebo. The primary endpoint was change in total body fat mass measured by dual-energy X-ray absorptiometry (DXA). In the intention-to-treat analysis, the adjusted between-group difference in change in body fat mass was − 1.59 kg (95% CI − 2.50 to − 0.67; p < 0.001), with consistent findings in the per-protocol (PP) analysis (− 1.54 kg; 95% CI − 2.25 to − 0.83; p < 0.001). Significant reductions were also observed in body weight and BMI; body fat percentage was significant in the PP analysis only. Waist circumference, lipid parameters, adiponectin, and inflammatory markers did not differ between groups. No treatment-related serious adverse events were reported. In conclusion, CAB701 supplementation for 12 weeks significantly reduced DXA-measured body fat mass and was well tolerated. These findings support the potential of CAB701 as a strain-specific functional probiotic for the reduction of adiposity in humans. This trial was registered in clinicaltrials.gov with registration number NCT06628791.

Polymer type drives successional structural and functional organization of plastisphere microbial networks - Kyu-Young Shim; In-Cheol Yeo; Euihyeon Lee; Hyun-Jung Kim; Kang Eun Kim; Jiezhang Mo; Youn-Jung Kim; Chang-Bum Jeong (Marine Environmental Research, 2026)

Comprehensive Approaches to Mitigating Heavy Metals and Metalloids Contamination: Plant Mechanisms, Biotechnological Advances, and Strategic Interventions - Ibrahim Khan; Sajjad Asaf; Lubna; Sang-Mo Kang; In-Jung Lee (Water, Air, & Soil Pollution, 2026)

Microphysiological system-based respiratory toxicity assessment: recent advances and regulatory perspectives - In Jae Bang; Min-Seok Kim; Yubin Han; Ga Eun Kim; Jung Eun Lim; Ji Yeong Park; Jin Yoo; Young Seo Jang; Beomhee Lee; Minjin Kwak; Soojin Park; Wonjun Jang; et al. (Toxicological Research, 2026)

Occupational risk assessment of p-tert-butylphenol: toxicity reference values and worker exposure evaluation - In Jae Bang; Ji Hyun Yu; Jung Eun Lim; Yubin Han; Yerim Koo; Damee Eun; Daeyeop Lee; Ig-Chun Eom; Ha Ryong Kim (Toxicological Research, 2026)

Effects of Clinostat rotation on stem morphology of Pisum Sativum - Sang-Min Kim; Jung-Hoo Kook; Jeong-In Choi; Oluwasegun Moses Ogundele; Won-Cheol Lee; Hyeon-Tae Kim (Life Sciences in Space Research, 2026)

Dielectric oligonucleotide fragments enable ultralow threshold photomultiplication in infrared quantum dot photodetectors - Yongnam Ahn; Jinwoo Shin; Woo Hyuk Jung; Yong Ho Cho; Minjung Yang; In-Suh Lee; Jaewoo Jeong; Taeho Han; Seoryeon Jeong; Jin Ah Lee; Chae Hyeong Ha; Yoon Jang Chung; et al. (Chemical Engineering Journal, 2026)

Interaction of SFPQ with S100A8 and S100A9 in EoL-1 and EoL-1-IR cells - Jae Ha Baek; Geunyeong Kim; Yujin Hong; Min Hwa Hong; Ji-Sook Lee; Ik-Chan Song; Soo-Jung Gong; In Sik Kim (Molecular & Cellular Toxicology, 2026)

Heavy metals in carbonated waters and beverages on the South Korean market - Yongcheol Lee; Hyuny Clark-Shim; Min-Su Chang; In-Sook Lee; Yun-Jung Yi; Hyun-Jeong Kim (Food Additives & Contaminants Part B-Surveillance, 2026)

Patterns of genomic variation and population structure suggest the strong influence of allopatry between peninsular and island distributions of seashore spatulate aster on the Korean east coast region - Homervergel G. Ong; Eui‑Kwon Jung; Woo-Ho Kim; Yong‑In Kim; Jung‑Hoon Lee; Bo‑Yun Kim; Young‑Dong Kim (Journal of Plant Research, 2026)

Functional characterization and enhanced production of extracellular vesicles from lactic acid bacteria using red light-emitting diodes - Su Yeon Park; Hyun Jin Na; In-Geun Jung; Do Yup Lee; Yeong Ji Oh (Biocatalysis and Agricultural Biotechnology, 2026)

Green-Synthesized Silver Nanoparticles Enhance Soybean Tolerance to Cadmium through Redox Regulation and Metabolic Reprogramming - Shifa Shaffique; Muhmmad Farooq; Muhmmad Saleem Khan; Ali Umar; Muhammad Aaqil Khan; Sang-Mo Kang; In-Jung Lee (Journal of Soil Science and Plant Nutrition, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

Bulliform cells: anatomical, physiological, genetic, and computational perspectives on plants’ drought adaptation - Ibrahim Khan; Sajjad Asaf; Sikandar Khan; Sohail Ahmad Jan; In-Jung Lee; Sang-Mo Kang (Planta, 2026)

Quantifying the joint effects of soil salinity and fertility on rice growth and yield variability in coastal paddies of southwestern Korea - Seo-Woo Park; Nuri Baek; Se-In Lee; Eun-Seo Shin; Hyun-Jin Park; Han-Yong Kim; Kyo-Suk Lee; Kwang-Seung Lee; Nurgul Kitir Sen; Woo-Jung Choi (Journal of Soils and Sediments, 2026)

Development of a Two-Set Multiplex PCR System for Rapid Discrimination of Seven Commercially Important Cuttlefish Species Using COI-Derived SNP Markers - Chun Mae Dong; Mi-Nan Lee; Hee Jeong Park; Hyo Sun Jung; Eun Soo Noh; In Joon Hwang; Jung-Ha Kang; Eun-Mi Kim (Fishes, 2026)
Reliable identification of seafood species is critical for fisheries management and product authentication, especially when morphological characteristics are lost during processing. In this study, a multiplex PCR system was developed to distinguish seven cuttlefish species (six Sepia spp. and Sepiella inermis) commercially distributed in the Korean seafood market. Species identity was first confirmed by amplifying a mitochondrial cytochrome c oxidase subunit I (COI) fragment (~658 bp) using universal primers (LCO1490/HCO2198), showing 99–100% sequence similarity to corresponding GenBank reference sequences. Analysis of genetic variation based on a 530 bp aligned region demonstrated complete interspecific differentiation without shared haplotypes among species. The number of haplotypes per species ranged from 5 to 21, with haplotype diversity values between 0.667 and 1.000. An extended COI fragment (~1200 bp) was further analyzed to identify diagnostic interspecific variation for marker development. Seven diagnostic single-nucleotide polymorphism (SNP) sites were identified and used to design species-specific forward primers with diagnostic nucleotides positioned at the 3′ termini. Distinct amplicons (220–1099 bp) were generated and clearly resolved by agarose gel electrophoresis. Because simultaneous amplification of all seven primer pairs reduced amplification efficiency, the assay was divided into two multiplex sets. Under optimized conditions (56 °C), each species produced a single expected band without cross-amplification. This multiplex PCR system provides a rapid and sequencing-free approach for reliable species discrimination and can be effectively applied to fisheries monitoring and seafood authentication in commercial supply chains.

Calcium carbonate hybrid microcomposite for oral delivery of luteolin, a poorly water-soluble phytocompound - Jung-Ki Hong; Yeji Kang; Seong-Wook Seo; Ji-Su Kong; Gayeong Lee; Chan Hee Lee; Jongwook Jeong; Ee Taek Hwang; In-Soo Yoon (Food Chemistry, 2026)

Pollution characteristics of PM2.5 and PM1.0 at urban and background sites in South Korea: Focusing on health risks of PAHs and heavy metals - Sang-Jin Lee; Ho-Young Lee; In-Gyu Cho; Seong-Joon Kim; Ji Yi Lee; Hye-Jung Shin; Young Sung Ghim; Yong Pyo Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Probiotic-Derived Strain-Specific Metabolites Ameliorate Metabolic Dysfunction–Associated Steatotic Liver Disease through Modulation of the Gut-Liver Axis - Sang Jun Yoon; Jieun Choi; Sung-Min Won; Jeong Seok Yu; Hee Young Kim; Hyun Chae Joung; In Gyu Park; Jung A Eom; Sang Hak Han; Do Yup Lee; Ki Tae Suk (Probiotics and Antimicrobial Proteins, 2026)

Correction to: Deep learning prediction of steep and flat corneal curvature using fundus photography in post‑COVID telemedicine era - Joon Yul Choi; Hyungsu Kim; Jin Kuk Kim; In Sik Lee; Ik Hee Ryu; Jung Soo Kim; Tae Keun Yoo (Medical & Biological Engineering & Computing, 2026)

Mapping of major QTLs for flowering time, seed weight, and oil content in a recombinant inbred line population of perilla - Jung-In Kim; Yeon Ju An; Myoung Hee Lee; Sang Woo Kim; Sungup Kim; Jeongeun Lee; Ki Young Kim; Tae-Hwan Jun; Eunsoo Lee (Euphytica, 2026)

Multiplex PCR Assay for the Rapid and Accurate Identification of Three Chionoecetes Species - Chun Mae Dong; Hee Jeong Park; Eun Soo Noh; Seung-Hwan Lee; In Joon Hwang; Jung-Ha Kang; Hyo Sun Jung (Fishes, 2026)
In this study, a multiplex PCR assay was developed for the rapid and accurate identification of three Chionoecetes species (Chionoecetes bairdi, C. opilio, and C. japonicus) available in global seafood markets. The morphological similarity between imported female C. bairdi from Japan and native C. opilio in Korea complicates visual discrimination and raises concerns over potential mislabeling. To address this issue, mitochondrial cytochrome c oxidase subunit I (COI) gene sequences were analyzed to identify species-specific SNPs, and primers were designed accordingly. Singleplex PCR confirmed species-specific amplification among the three target species, and the optimal annealing temperature was determined. The multiplex PCR simultaneously amplified distinct fragments of 598 bp (C. bairdi), 401 bp (C. opilio), and 194 bp (C. japonicus), with no nonspecific amplification or primer–dimer formation. Sensitivity testing revealed a detection limit of 0.01 ng/µL for all three species, defined as the lowest DNA concentration at which species-specific bands were consistently observed in at least two out of three replicates. These results demonstrate that the developed multiplex PCR is a reliable, rapid, and cost-effective tool for accurate species identification, supporting sustainable resource management, preventing seafood fraud, and ensuring safe distribution in both Korea and global seafood markets.

A single urine test-based SERS–AI–BAM for on-site multiple cancer diagnosis and metabolite profiling - Hyo Jeong Seo; Jun Young Kim; Vo Thi Nhat Linh; Boyou Heo; Jun-Young Yang; Rowoon Park; In Woong Han; Sung-Gyu Park; Min-Young Lee; Samjin Choi; Ho Sang Jung (Chemical Engineering Journal, 2026)

Transcriptomic Signatures of Interspecific Brassica Hybrids Reveal the Molecular Basis of Viviparous Seed Development - Muthusamy Muthusamy; Pandian Subramani; In-Jung Lee; Yoonha Kim; Eun-Kyoung Shin; Young-Ju Oh; Soo In Sohn (Journal of Plant Growth Regulation, 2026)

The barley ERF factor HvRAF enhances tillering and grain yield in transgenic rice by modulating cytokinin–gibberellin homeostasis - Jaemin Hwang; Sang-Mo Kang; Eun-Hae Kwon; In-Jung Lee; Jun Sung Seo; Minkyun Kim (Plant Biotechnology Reports, 2026)

Substitution of lithogenic with pedogenic soil carbonates in Korean coastal rice paddy under desalinization: Evidences from δ13C - Seo-Woo Park; Nuri Baek; Eun-Seo Shin; Bo-Seong Seo; Se-In Lee; Kwang-Seung Lee; Seok-In Yun; Hyun-Jin Park; Sang-Mo Lee; Woo-Jung Choi (Agriculture, Ecosystems & Environment, 2026)

Investigation on Wake Characteristics of Two Tidal Stream Turbines in Tandem Using a Mobile Submerged PIV System - Sejin Jung; Heebum Lee; In Sung Jang; Seong Min Moon; Heungchan Kim; Chang Hyeon Seo; Jihoon Kim; Jin Hwan Ko (Journal of Marine Science and Engineering, 2026)
Understanding wake interactions between multiple tidal stream turbines is essential for optimizing the performance and layout of tidal energy farms. This study investigates the hydrodynamic behavior of two horizontal-axis tidal turbines arranged in tandem under simplified inflow conditions, where the incoming flow was dominated by the streamwise velocity component without imposed external disturbances. Wake measurements were conducted in a large circulating water tunnel using a mobile, submerged particle image velocimetry (PIV) system capable of long-range, high-resolution measurements. Performance tests showed that the downstream turbine experienced a decrease of approximately 9% in maximum power coefficient compared to the upstream turbine due to reduced inflow velocity and increased turbulence generated by the upstream wake. Phase-averaged PIV results revealed the detailed evolution of velocity deficit, turbulence intensity, turbulent kinetic energy, and tip vortex structures. The tip vortices shed from the upstream turbine persisted over a long downstream distance, remaining coherent up to 10D and merging with those generated by the downstream turbine. These merged vortex structures produced elevated turbulence and complex flow patterns that significantly influenced the downstream turbine’s operating conditions. The results provide experimentally validated insight into turbine-to-turbine wake interactions and highlight the need for high-fidelity wake data to support array optimization and numerical model development for tidal stream turbine array.

Evaluation and application of molecular marker sets for developing PHS-resistant wheat in Korea - Hyeonjin Park; Jin-Kyung Cha; So-Myeong Lee; Youngho Kwon; Woo-Jae Kim; Jong-Hee Lee; In-Jung Lee (Euphytica, 2026)
Pre-harvest sprouting (PHS) is a major constraint on wheat production in Korea, reducing grain quality and end-use value. To accelerate the development of PHS-resistant cultivars with improved agronomic performance, we employed a marker-assisted backcrossing (MABC) approach using molecular markers previously reported in the literature. For foreground selection, 81 molecular markers (74 KASP and 7 gel-based) targeting key genes related to PHS resistance, grain quality, and disease resistance were applied. Genome-wide background selection was conducted with 547 KASP markers to monitor recovery of the recurrent parent genome. Genotyping of 94 wheat accessions revealed distinct genetic clustering among domestic cultivars, introduced germplasm, and 1BL.1RS rye translocation lines, demonstrating the effectiveness of the marker set in capturing genome-wide diversity. Using MABC combined with speed breeding, three elite lines were developed by pyramiding favorable alleles from ‘Joongmo2008’ and ‘Tapdong’. Among them, ‘Milyang55’ exhibited strong PHS resistance (germination rate: 21.1%), desirable agronomic traits, and flour quality comparable to ‘Joongmo2008’. Donor genome proportions ranged from 25.5 to 43.0%, confirming efficient recovery of the recurrent parent genome. These results highlight the utility of integrating pre-selected molecular markers with MABC and speed breeding for the rapid development of elite wheat cultivars with improved PHS resistance and end-use quality.

Evaluation of total nitrogen stocks and burial rates in salt marshes and bare flats of Marine National Parks in South Korea - Inha Kwon; Taewoo Kim; Seo Joon Yoon; Shin Yeong Park; In Ok Lee; Dong-U Kim; Hosang Kim; Cheongjae Lee; Young Eun Kim; Changkeun Lee; Bong-Oh Kwon; Jung Kwan Ahn; et al. (Regional Studies in Marine Science, 2025)

Multi-objective optimization of ultra-low temperature Joule-Thomson cycle using CO₂-based eco-friendly and non-flammable zeotropic mixtures as sustainable refrigerant alternatives - Sang-Chan Park; Jung-In Yoon; Chang-Hyo Son; Sung-Hoon Seol; Joon-Hyuk Lee (International Journal of Refrigeration, 2025)

Thermal processing effects on phytochemical profiles, antioxidant activity, and anti-inflammatory potential of extracts from dried rhizomes of Curcuma longa L. evaluated by UHPLC–MS/MS and in vitro assays - Choong-In Yun; Min-A Kim; Sung Keun Jung; Young-Jun Kim; JaeHwan Lee (Food Chemistry, 2025)

Consortium of Endophytic Bacillus australimaris CK11 and Staphylococcus epidermidis CK9 from Commiphora gileadensis Mediates Tomato Resilience to Combined Salinity, Heat, and Drought Stresses - Syed Saad Jan; Nasir Ali Khan; Sajjad Asaf; Raheem Shahzad; Lubna; Muhammad Imran; Saqib Bilal; In-Jung Lee; Ahmed Al-Harrasi (Journal of Plant Growth Regulation, 2025)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

Hybrid W-MgF2/graphene photothermal membrane for efficient solar-driven desalination - Ga Eun Lee; Jinsoo Cho; In-Young Jung; Da Seul Kim; Seok Joon Kwon; Won Jun Choi; Kyung Guen Song; Hak Ki Yu; Jeong Min Baik (Desalination, 2025)

3D liver model for assessing immune-mediated hepatotoxicity from biopharmaceutical risks - Mi-lang Kyun; Duhyeon Park; Hyewon Jung; Ji Hyeon Ryu; Inhye Kim; Seo Yule Jeong; Jeongha Kim; Minseong Jo; Ji-In Kwon; Ju-Kang Kim; Dahong Kim; Su A. Park; et al. (Chemical Engineering Journal, 2025)

Collagenase and tyrosinase inhibitory compounds from fish gut bacteria Ruegeria atlantica and Pseudoalteromonas neustonica - Jonghwan Kim; Su Jung Hwang; Gyu Sung Lee; Ju Ryeong Lee; Hye In An; Hong Sik Im; Minji Kim; Sang-Seob Lee; Hyo-Jong Lee; Chung Sub Kim (Phytochemistry Letters, 2025)

Study on modulation of inflammation expression by Brassica oleracea L. leaves extract - Jung-Wook Kang; Dan-Hee Yoo; Hyo-Min Kim; Ji-Won Hur; Kyeung-A Kwon; Kyung-Eun Lee; Min-Yeong Kim; Yong-Jun Kwon; Su-Bin Yu; Ju-Hyun Park; In-Chul Lee (Phytochemistry Letters, 2025)

A study on the biological activities of loquat leaf extract using various extraction methods - Jung-Wook Kang; Suk-Min Son; In-Chul Lee (Phytochemistry Letters, 2025)

Green solvent-based highly permeable PES membranes for virus filtration in bioprocesses - Chang-Hun Kim; Eunwoo Jung; In-Chul Kim; Mi-Hee Ryu; Jung-Hyun Lee; Youngbin Baek; Young Hoon Cho (Chemical Engineering Journal, 2025)

High-purity Li₆PS₅Cl sulfide solid electrolytes via liquid-phase method synthesis for high-performance all-solid-state Li-ion batteries: Particle-scale analysis of formation with precursor and solvent optimization - Hyewon Jo; Bitna Kim; Byeong-Min Ahn; Youngjun Huh; Soyoung Kim; Jung Han Kim; Heetaek Park; Jun-Woo Park; Yoon-Cheol Ha; Jay Hyok Song; Je In Lee; Jun-Ho Park (Chemical Engineering Journal, 2025)

Utilizing artificial intelligence techniques for soil depth prediction and its influences in landslide hazard modeling - Ananta Man Singh Pradhan; Suchita Shrestha; Jung-Hyun Lee; In-Tak Hwang; Hyuck-Jin Park (Stochastic Environmental Research and Risk Assessment, 2025)

Floral development and phenolic compounds production in Agastache rugosa through light regulation - Yun Ji Park; Su Hyeon Lee; Hyo In Yoon; Jai-Eok Park; To Quyen Truong; Je Hyeong Jung; Jung-Seok Yang; Inkyu Park; Sang Min Kim (Planta, 2025)

Preclinical Pharmacokinetics of DM5167, a Novel Selective PARP1 Inhibitor - Jin Woo Kim; Seung-Won Lee; Myung Eun Jung; Ki-Hong Jang; Hae-In Choi; Yoon Ha Lee; Jeongmin Kim; Sunjoo Ahn; Eunhee Kim; Tae-Sung Koo (Pharmaceutical Research, 2025)

ELF18-INDUCED LONG NONCODING RNA 25 positively regulates the pathogen defense-related CYP82C2 expression in Arabidopsis - Jun Sung Seo; Moon-Joo Lee; Jimin Lee; Nuri Oh; So-Young Jang; Ye In Cho; Jin-Ho Kang; Jang-Kyun Seo; Hye Sun Cho; Moonhyuk Kwon; Choonkyun Jung (Journal of Plant Biology, 2025)
Long noncoding RNAs (lncRNAs) are emerging as important regulators of gene expression during plant immune responses. In this study, we identified a novel lncRNA, ELF18-INDUCED LONG NONCODING RNA 25 ( ELENA25 ), located in the intergenic region between AT4G31960 and CYTOCHROME P450, family 82, subfamily C, polypeptide 2 ( CYP82C2 ) in Arabidopsis. ELENA25 was initially identified through custom lncRNA microarray data. Here, its full-length sequence (810 bp) was determined using primer walking and confirmed by sequencing. ELENA25 expression was preferentially induced by flg22, a bacterial pathogen-associated molecular pattern (PAMP), in a late-phase and FLS2 receptor-dependent manner. Neighboring genes AT4G31960 and CYP82C2 were also flg22-inducible, with expression abolished in the fls2 mutant background. To assess whether ELENA25 regulates the expression of nearby genes, we generated ELENA25 -overexpressing (OX) and knockout (KO) plants. In ELENA25 OX lines, CYP82C2 expression was significantly upregulated under normal and flg22-treated conditions, while AT4G31960 expression remained unchanged. Conversely, in the elena25 mutants (KO), CYP82C2 expression was significantly reduced, indicating that ELENA25 positively regulates CYP82C2 transcription. Expression levels of other nearby cytochrome P450 genes, including CYP82C3 and CYP82C4 , and other indole glucosinolate-related CYP genes were not affected by ELENA25 expression changes. Collectively, our results demonstrate that ELENA25 is a flg22-inducible lncRNA that specifically enhances CYP82C2 expression in a FLS2-dependent manner. This study provides new insights into the role of lncRNAs in plant innate immunity, highlighting ELENA25 as a positive regulator of defense-related gene expression.

Strain-Specific Effects of Bacillus subtilis, Enterococcus faecium, and Pediococcus pentosaceus Supplementation on Growth Performance, Immunity, and Disease Resistance in Olive Flounder (Paralichthys olivaceus) - Min-Kyeong Lee; Hyun-Kyoung Jung; Dong-Gyun Kim; In-Suk Park; Yu Li Heo; Jungha Kang; Young Sam Kim (Fishes, 2025)
Olive flounder (Paralichthys olivaceus), a key aquaculture species in East Asia, is prone to stress and bacterial diseases under intensive farming. Antibiotics are often used to control these problems, but their overuse promotes resistance and threatens sustainability. To provide safer alternatives, this study evaluated the strain-specific effects of dietary probiotics on growth, immunity, and disease resistance in olive flounder. A five-week feeding trial was conducted to evaluate the effects of three isolates—Bacillus subtilis, Enterococcus faecium, and Pediococcus pentosaceus—on growth, blood biochemistry, immune responses, and resistance against Edwardsiella tarda. Each strain was incorporated individually into a basal diet. After the feeding trial, probiotic supplementation improved growth performance. P. pentosaceus significantly increased final body weight and other growth indices (p

Emergence of a conjugative hybrid plasmid co-harboring mcr-1.1, mcr-3.39, and tet(X4) in Escherichia coli from wastewater in Seoul: A potential threat to last-line antibiotics - Jin Seok Kim; Young Hee Jin; Jinwoo Kim; Chang-Kyu Kim; Sook Hyun Park; Ahryung Oh; YoungAh Yoo; Jae In Lee; Jihun Jung (Science of The Total Environment, 2025)

AI-driven multivariate time series forecasting of transmembrane pressure in ultrafiltration: A stationarity-aware approach - Dongju Kim; Jong Pil Yun; Taehan Lee; Daewoong Jung; Hong-In Won (Journal of Water Process Engineering, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Physicochemical characterization and in vivo assessment of novel apixaban-loaded polymeric nano-aggregates - Fakhar ud Din; Hye In Lee; Jung Suk Kim; Mi Ran Woo; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Garlic as a modulator of bacterial dynamics and metabolite profiles in kimchi fermentation - Min Ji Kim; Sera Jung; Hyun-Sung Kim; Ji Young Jeong; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Bioscience, 2025)

Seasonal dynamics of picocyanobacteria and bloom-forming cyanobacteria in Daechung Reservoir, Korea - Hye Jeong Choi; In-Chan Choi; So Hyun Cho; Eun-mi Hong; Jay Jung Lee (Paddy and Water Environment, 2025)

Development of validated ultrasensitive enzyme-linked immunosorbent assay method of human epidermal growth factor and in vivo pharmacokinetic study - Dong Ho Oh; Sang-Ok Jeon; Min Ju Kim; Jo-Eun Seo; Taekwang Keum; Gyubin Noh; Dong-Gyun Han; In-Soo Yoon; Chae-Ha Yoon; Jung-Eun Choo; Sangkil Lee (Journal of Pharmaceutical Investigation, 2025)

Development of a novel apixaban-loaded solid self-emulsifying drug delivery system for oral administration: physicochemical characterization and pharmacokinetics in rats - Hye In Lee; Mi Ran Woo; Fakhar ud Din; Jung Suk Kim; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Development of a deep neural network model based on high throughput screening data for predicting synergistic estrogenic activity of binary mixtures for consumer products - Jongwoon Kim; Seung-Jin Lee; Daeyoung Jung; Hyun Young Kim; Jung-In Lee; Myungwon Seo; Sunmi Kim; Jiwon Choi; Wook-Joon Yu; Heeyeong Cho (Journal of Hazardous Materials, 2025)

Exploration of formate as a liquid organic hydrogen carrier in biohydrogen production through evolutionary and process engineering of hyperthermophilic archaeon - Hae-Chang Jung; Sung-Mok Lee; Ji-in Yang; Seong Hyuk Lee; Hyun Sook Lee; Sung Gyun Kang (Bioresource Technology, 2025)

Thermal maturity and colors of Cretaceous East Asian fossil eggs - Seung Choi; Shukang Zhang; Noe-Heon Kim; Jin Jung Kweon; Kohei Tanaka; Katsuhiro Kubota; Yuong-Nam Lee; Junfang Xie; In Sung Paik; Sung Keun Lee (Sedimentary Geology, 2025)

Correction to: PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2025)

Multiple measures to mitigate methane emissions from organic rice fields: a review and future challenges - Nuri Baek; Se-In Lee; Husna Israt Pia; Seo-Woo Park; Eun-Seo Shin; Miwa M. Yashima; Han-Yong Kim; Hyun-Jin Park; Woo-Jung Choi (Journal of Soils and Sediments, 2025)

Implementing Seoul's greenhouse gas management in buildings: Insights from the SICE model - In Chang Hwang; Yoonhye Yi; Hyun-jung Lee; Jong-rak Baek (Energy Policy, 2025)

Key phase diagram experiment of the ZnO-SnO2 system and thermodynamic modeling of the ZnO-SnO2-TiO2 system - Jaesung Lee; Yoongu Kang; In-Ho Jung (Physics and Chemistry of Minerals, 2025)

Monitoring of organochlorine pesticides using pine needle, pine bark, and soil samples across South Korea: Source apportionment and implications for atmospheric transport - Sanjenbam Nirmala Khuman; Ho-Young Lee; In-Gyu Cho; David Chung; Soo Yong Lee; Jangho Lee; Jung-Keun Oh; Sung-Deuk Choi (Chemosphere, 2025)

Transparent and visible light-activated antimicrobial air filters from electrospun crystal violet-embedded polyacrylonitrile nanofibers - Seung Yeon Lee; Jae Hak Shin; In Ho Kim; Dong Yun Choi; Dong Uk Lee; Gi Byoung Hwang; Bangwoo Han; Sang Bok Kim; Dong-Keun Song; Inyong Park; Jae Hee Jung (Environmental Research, 2025)

Development of a comprehensive air risk index and its application to high spatial-temporal health risk assessment in a large industrial city - Sang-Jin Lee; In-Gyu Cho; Ho-Young Lee; Jeong-Tae Ju; Hye-Jung Shin; Sung-Deuk Choi (Environmental Pollution, 2025)

NXP032 Improves Memory Impairment Through Suppression of Tauopathy in PS19 Mice and Attenuates Okadaic Acid-Induced Tauopathy in SH-SY5Y Cells - Hyeyoon Eo; Seong Hye Kim; In Gyoung Ju; Joo Hee Lee; Myung Sook Oh; Youn-Jung Kim (Journal of Neuroimmune Pharmacology, 2025)

Patent bigdata in plant cultivation technology including promising breeding technologies: a comparative study of intellectual properties leading five countries - JaeHeon Lee; GiHo Ryu; In-Jung Kim (Plant Biotechnology Reports, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Enhancement of renal fibrosis in PHF20 transgenic mice - Uijin Juang; Soohyeon Lee; Suhwan Gwon; Woohyeong Jung; Huonggiang Nguyen; Qingzhi Huang; Beomwoo Lee; So Hee Kwon; Seon-Hwan Kim; In Soo Kim; Jongsun Park (Toxicological Research, 2025)

Role of Rab proteins in PFOA-induced changes in boar sperm motility and capacitation - Seung-Ik Jang; Jae-Hwan Jo; Claudine Uwamahoro; Eun-Ju Jung; Woo-Jin Lee; Jeong-Won Bae; Sangsu Shin; Sang In Lee; Myoung Ok Kim; Joonho Moon; Woo-Sung Kwon (Reproductive Toxicology, 2024)

UV photoreduction-driven heterogeneous fenton-like process: Long-term reactivation of fenton sludge-derived biochar and enhanced acetaminophen degradation - Heejin Yang; Sung-Hyo Jung; Jong Ho Lee; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Journal of Water Process Engineering, 2024)

Nationwide analysis of greenhouse effluents reveals robustness of crops as a modulator of ambient stoichiometry - Tae In Ahn; Jung-Seok Yang; Yong-Hoon Im; Young Jik Youn; Dahae Kim; Ju Young Lee (Journal of Cleaner Production, 2024)

Preparation of fragmented polyethylene nanoplastics using a focused ultrasonic system and assessment of their cytotoxic effects on human cells - Seonae Hwangbo; In Young Kim; Kwanyoung Ko; Kyungtae Park; Jinkee Hong; Gwansuk Kang; Jung-Sub Wi; Jaeseok Kim; Tae Geol Lee (Environmental Pollution, 2024)

Optimization of hierarchical textured PDMS film with wide-angle broadband anti-reflection for light trapping in solar cells - Hanbin Lee; Sangmin Chae; Ahra Yi; Vasanthan Devaraj; Jin-Woo Oh; In Hwa Cho; Hyo Jung Kim (Chemical Engineering Journal, 2024)

Genetic dissection of resistance to Phytophthora sojae using genome-wide association and linkage analysis in soybean [Glycine max (L.) Merr.] - Hee Jin You; Ik Hyun Jang; Jung-Kyung Moon; In-Jeong Kang; Ji-Min Kim; Sungtaeg Kang; Sungwoo Lee (Theoretical and Applied Genetics, 2024)

Effects of exotic Spartina alterniflora invasion on benthic environments in the Yellow Sea - Jongmin Lee; Junsung Noh; Changkeun Lee; In Ok Lee; Inha Kwon; Bong-Oh Kwon; Moo Joon Lee; Jung-Ho Lee; Jongseong Ryu; Jinhyun Kim; Hojeong Kang; Ho Kyung Ha; et al. (Marine Pollution Bulletin, 2024)

Effect of activated carbon-based two-stage adsorption on biogenic amine reduction and quality of anchovy fish sauce at industrial scale - Jung-Jin In; Kil Bo Shim; Jong Bong Lee; Yeon Joo Bae; Ga Yeon Kwon; Hyo Rim Lee; Sunhyun Park; Suk Kyung Sohn (Food Chemistry, 2024)

Hepatocyte-specific RIG-I loss attenuates metabolic dysfunction-associated steatotic liver disease in mice via changes in mitochondrial respiration and metabolite profiles - Jin Kyung Seok; Gabsik Yang; Jung In Jee; Han Chang Kang; Yong-Yeon Cho; Hye Suk Lee; Joo Young Lee (Toxicological Research, 2024)

Establishment of a small-cell lung cancer (SCLC) mouse model using enhanced cancer stem-cell-functioning 3D SCLC spheroids - Yong Hun Jung; In Kyoung Kim; So Young Eom; Hyunsoo Kim; Kyungwon Park; Seok Chung; Sang Haak Lee; Chang Dong Yeo; Hye Joung Kim; Hye Seon Kang (Molecular & Cellular Toxicology, 2024)

T cell receptor clonotype in tumor microenvironment contributes to intratumoral signaling network in patients with colorectal cancer - In Hye Song; Seung-been Lee; Byung-Kwan Jeong; Jungwook Park; Honggeun Kim; GunHee Lee; Su Min Cha; Heejae Lee; Gyungyub Gong; Nak-Jung Kwon; Hee Jin Lee (Immunologic Research, 2024)

Enhancing machine learning models for total organic carbon prediction by integrating geospatial parameters in river watersheds - Haeseong Oh; Ho-Yeon Park; Jae In Kim; Byung Joon Lee; Jung Hyun Choi; Jin Hur (Science of The Total Environment, 2024)

Microcystis abundance is predictable through ambient bacterial communities: A data-oriented approach - Mingyeong Kang; Dong-Kyun Kim; Ve Van Le; So-Ra Ko; Jay Jung Lee; In-Chan Choi; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Journal of Environmental Management, 2024)

Design and Simulation-Based Validation of an AI Model for Predicting Grab-Type Ship Unloader Operation Data - Ga-Eun Jung; Woo-Hee Jeong; Seok-Ju Lee; Jae-In Lee; Tae-Won Kim; Hae-Jin Sung (Journal of Marine Science and Engineering, 2024)
Along with seaports automation, there is growing interest in the automation of Grab-Type Ship Unloader (GTSU) that unloads coal and iron ore from bulk carriers. Autonomous unloading operations of GTSU offer the potential for significant productivity improvement and cost savings. In this paper, an AI model trained with manual operation data was designed for GTSU automation operation, and the AI model was verified through the equation-of-motion-based GTSU operation simulator. The operation data of hoist, grab, and trolley were predicted by training the designed AI model with the manual operation data of GTSU. Before applying the predicted data to the actual equipment, the predicted driving data was verified using the equation-of-motion-based GTSU operation simulator. The AI prediction model was designed using the Multi-Layer Perception network, a type of artificial neural network. The AI prediction model was evaluated with the Mean-Squared Error indicator, and the validation loss was found to be less than 0.02. In addition, verification of the prediction data was performed using the GTSU dynamics-based simulator. The Mean Relative Error was up to 0.50, and the R2 score value exceeded 0.92, indicating that the model is effective in predicting operation data. The proposed AI prediction model will be effectively utilized to implement a fully automated unloading system.

Evolution-aided improvement of the acid tolerance of Levilactobacillus brevis and its application in sourdough fermentation - Na Ree Han; Sora Yu; Jung A Byun; Eun Ju Yun; Seongwon Cheon; Seongbong Song; Sangmin Shim; In-Geol Choi; Sung-Ho Lee; Kyoung Heon Kim (Food Research International, 2024)

Green aluminum metal-organic frameworks (Al-MOFs) supported on commercial activated carbon for enhanced removal performances of industrial fluoride pollutants - U.T. Uthappa; Kanalli V. Ajeya; Veeman Sannasi; Sang Goo Lee; Eun-Ho Sohn; Bong-Jun Chang; In-Jun Park; Ju Hyeon Kim; Mahaveer D. Kurkuri; Ho-Young Jung (Journal of Water Process Engineering, 2024)

A heterostructured ternary transition metal oxide composite as an efficient electrocatalyst for the hydrogen evolution reaction - Soo Hong Lee; Seunghwan Jo; Jeong In Jeon; Jung Inn Sohn; John Hong (Journal of Environmental Chemical Engineering, 2024)

Effects of the physical structure and surface charge of activated carbon on the reduction of biogenic amines in anchovy fish sauce - Kil Bo Shim; Jung-Jin In; Jong Bong Lee; Hyeong Gu Han; Seong Ah Son; Woo Jin Lee; Yeon Joo Bae; Ga Yeon Kwon; Byoung Kyu An (Food Chemistry, 2024)

Unique photothermal material: Copper phosphate (Cu3P2O8) with broadband visible-to-near-infrared absorption properties for efficient solar steam generation - Tatachari Santhanagopalan Shridharan; Jong Ho Lee; Runfa Tan; Arumugam Sivanantham; Hyun Soo Han; Hyun Suk Jung; In Sun Cho (Desalination, 2024)

Correction to: Comparison of skin dose in IMRT and VMAT with TrueBeam and Halcyon linear accelerator for whole breast irradiation - Jae Hyun Seok; So Hyun Ahn; Woo Sang Ahn; Dong Hyeok Choi; Seong Soo Shin; Wonsik Choi; In-hye Jung; Rena Lee; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2024)

Comparison of skin dose in IMRT and VMAT with TrueBeam and Halcyon linear accelerator for whole breast irradiation - Jae Hyun Seok; So Hyun Ahn; Woo Sang Ahn; Dong Hyeok Choi; Seong Soo Shin; Wonsik Choi; In-hye Jung; Rena Lee; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2024)
With the increasing use of flattening filter free (FFF) beams, it is important to evaluate the impact on the skin dose and target coverage of breast cancer treatments. This study aimed to compare skin doses of treatments using FFF and flattening filter (FF) beams for breast cancer. The study established treatment plans for left breast of an anthropomorphic phantom using Halcyon’s 6-MV FFF beam and TrueBeam’s 6-MV FF beam. Volumetric modulated arc therapy (VMAT) with varying numbers of arcs and intensity modulated radiation therapy (IMRT) were employed, and skin doses were measured at five points using Gafchromic EBT3 film. Each measurement was repeated three times, and averaged to reduce uncertainty. All plans were compared in terms of plan quality to ensure homogeneous target coverage. The study found that when using VMAT with two, four, and six arcs, in-field doses were 19%, 15%, and 6% higher, respectively, when using Halcyon compared to TrueBeam. Additionally, when using two arcs for VMAT, in-field doses were 10% and 15% higher compared to four and six arcs when using Halcyon. Finally, in-field dose from Halcyon using IMRT was about 1% higher than when using TrueBeam. Our research confirmed that when treating breast cancer with FFF beams, skin dose is higher than with traditional FF beams. Moreover, number of arcs used in VMAT treatment with FFF beams affects skin dose to the patient. To maintain a skin dose similar to that of FF beams when using Halcyon, it may be worth considering increasing the number of arcs.

Recent Advances in Biochemical Reprogramming Network Under Drought Stress in Soybean - Shifa Shaffique; Muhammad Farooq; Sang-Mo Kang; In-Jung Lee (Journal of Soil Science and Plant Nutrition, 2024)

Evaluation of Initial Fire Extinguishing System for Marine ESS - Seung-Yul Lee; In-Chul Park; Jeong-Hoon Park; Hyo-Seok Jung (Journal of Marine Science and Engineering, 2024)
A fire in a marine energy storage system (ESS) has a high risk because of the special situation of the sea compared with land systems. To mitigate serious damage in the event of a fire in marine ESSs, initial suppression of the fire is extremely important. In this study, a unit module-based fire extinguishing system was constructed for the initial suppression of an ESS fire, and a unit module fire suppression test was conducted. In addition, multiple modules were constructed to evaluate the impact of unit module fire suppression on adjacent modules. Novec 1230 and F-500, which are adaptable to ESS fire control, were used as extinguishing agents. The fire suppression test results showed that both extinguishing agents could effectively suppress the ESS fire in the initial stage using the proposed fire extinguishing system. The results of this study will contribute to the development of maritime safety protocols and practical measures for reinforcing preparation for ESS-related fire accidents.

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

A comparison of the nutritional quality of ready-to-cook meals and conventional home-cooked meals in Korea - Eunji Choi; Sung-Won Yoon; Jung-Ah Shin; In-Hwan Kim; Jeehye Sung; Jang-Hyuk Ahn; Hyun-Jeong Kim; Dong Won Seo; Sam-Pin Lee; Jo-Won Lee; Bo Kyung Moon; Sojung Kim; et al. (International Journal of Gastronomy and Food Science, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Cancer screening through surface-enhanced Raman spectroscopy fingerprinting analysis of urinary metabolites using surface-carbonized silver nanowires on a filter membrane - Ho-Jae Yu; Eunji Jang; Ayoung Woo; In Woong Han; Hwang Gyun Jeon; Vo Thi Nhat Linh; Sung-Gyu Park; Ho Sang Jung; Min-Young Lee (Analytica Chimica Acta, 2024)

Utilization of coffee waste as a sustainable feedstock for high-yield lactic acid production through microbial fermentation - Seulbi Kim; Jong-Cheol Kim; Yeong Yeol Kim; Jung Eun Yang; Hee Min Lee; In Min Hwang; Hae Woong Park; Ho Myeong Kim (Science of The Total Environment, 2024)

Bioconversion of citrus waste into mucic acid by xylose-fermenting Saccharomyces cerevisiae - Deokyeol Jeong; Sujeong Park; Grace Evelina; Suhyeung Kim; Heeyoung Park; Je Min Lee; Sun-Ki Kim; In Jung Kim; Eun Joong Oh; Soo Rin Kim (Bioresource Technology, 2024)

Considering the Chemical Components of Particulate Matter 2.5 for Assessing Its Health Risks to Residents near the Ansan/Siheung and Ulsan Industrial Complexes - Ji-Yun Jung; Shin-Young Park; Jeong-In Jeon; Hye-Won Lee; Sung-Won Yoon; Cheol-Min Lee (Water, Air, & Soil Pollution, 2024)

Deep learning prediction of steep and flat corneal curvature using fundus photography in post-COVID telemedicine era - Joon Yul Choi; Hyungsu Kim; Jin Kuk Kim; In Sik Lee; Ik Hee Ryu; Jung Soo Kim; Tae Keun Yoo (Medical & Biological Engineering & Computing, 2024)

Effect of nitro-conjugated linoleic acid on the inflammatory response of murine macrophages activated with lipopolysaccharide derived from Prevotella intermedia - Jung Eun Lee; Ah Rim Lee; Eun-Young Choi; In Soon Choi; Sung-Jo Kim (Inflammopharmacology, 2024)

Perfluorooctanoic acid suppresses sperm functions via abnormal Protein Kinase B activation during capacitation - Seung-Ik Jang; Jae-Hwan Jo; Eun-Ju Jung; Woo-Jin Lee; Ju-Mi Hwang; Jeong-Won Bae; Sangsu Shin; Sang In Lee; Myoung Ok Kim; Woo-Sung Kwon (Reproductive Toxicology, 2024)

Inhibitory effects of Oncorhynchus mykiss lipids in LPS-induced RAW264.7 cells via suppression of NF-κB and MAPK pathways - Yun Gu Gwon; Weerawan Rod-in; Ha Jun Lee; Sang-min Lee; Il-shik Shin; Woo Jung Park (Fish & Shellfish Immunology, 2024)

Dynamic Ti3+ and In3+ dual active sites on In2TiO5 to enhance visible-light-driven gas-phase photocatalytic CO2 reduction - Niket S. Powar; Myeongjin Jang; Min Gyu Kim; Chaitanya B. Hiragond; Junho Lee; Eunhee Gong; Hwapyong Kim; Dongyun Kim; Jin-Woo Jung; Chang-Hee Cho; Tierui Zhang; Minho Kim; et al. (Chemical Engineering Journal, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Anti-inflammatory and relaxation effects of Ulmus pumilla L. on EGF-inflamed bronchial epithelial and asthmatic bronchial smooth muscle cells - In-Seung Lee; Yeonjung Choi; Wona Jee; Jihyuk Park; Hyungsuk Kim; Kwanil Kim; Hee-Jae Jung; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2024)

Dynamic response of bacterial communities to Microcystis blooms: A three-year study - Ve Van Le; Mingyeong Kang; So-Ra Ko; Seonah Jeong; Chan-Yeong Park; Jay Jung Lee; In-Chan Choi; Hee-Mock Oh; Chi-Yong Ahn (Science of The Total Environment, 2023)

Performance comparison of photodynamic antimicrobial chemotherapy with visible-light-activated organic dyes: Rose bengal, crystal violet, methylene blue, and toluidine blue O - Jae Hak Shin; Sang Bin Jeong; In Ho Kim; Seung Yeon Lee; Gi Byoung Hwang; Inyong Park; Ki Joon Heo; Jae Hee Jung (Environmental Research, 2023)

Development of an In Vitro Model for Inflammation Mediated Renal Toxicity Using 3D Renal Tubules and Co-Cultured Human Immune Cells - Mi-lang Kyun; Tamina Park; Hyewon Jung; Inhye Kim; Ji-In Kwon; Seo Yule Jeong; Myeongjin Choi; Daeui Park; Yu Bin Lee; Kyoung-Sik Moon (Tissue Engineering and Regenerative Medicine, 2023)

Nifedipine attenuates alveolar bone destruction and improves trabecular microarchitectures in mice with experimental periodontitis - Yohan Lee; Jung Eun Lee; Ah Rim Lee; Eun-Young Choi; In Soon Choi; Sung-Jo Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Patterns of δ15N in forest soils and tree foliage and rings between climate zones in relation to atmospheric nitrogen deposition: A review - Woo-Jung Choi; Hyun-Jin Park; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sun-Il Lee; Seo-Woo Park; Eun-Seo Shin; Sang-Sun Lim (Science of The Total Environment, 2023)

Dual facet passivation of silver halometallate for eco-friendly silver bismuth sulfide near IR photodetector - Ashish Sharma; Hanjae Kim; Gunhee Kim; Jinhyeon Kang; Cheong Beom Lee; Sung Yong Bae; Hochan Song; Kyeounghak Kim; Jong Hyun Kim; In Hwan Jung; Dong-Won Kang; Jihoon Lee; et al. (Chemical Engineering Journal, 2023)

Development of high-performance organic photodetectors by understanding origin of dark current density with synthesis of photoconductive polymers - WonJo Jeong; Jinhyeon Kang; Dongchan Lee; Cheol Shin; Hyungju Ahn; Chan So; Jong Ho Won; Dae Sung Chung; Shinuk Cho; In Hwan Jung (Chemical Engineering Journal, 2023)

Association between SYVN1 and SEL1 genetic polymorphisms and remission in rheumatoid arthritis patients treated with TNF-α inhibitors: a machine learning approach - Woorim Kim; Ha Rim Yeon; Jun Hyeob Kim; Joo Hee Kim; Ji Hyoun Kim; Hyoun-Ah Kim; Ju-Yang Jung; Jinhyun Kim; In Ah Choi; Kyung Eun Lee (Immunologic Research, 2023)

Detection of microplastic traces in four different types of municipal wastewater treatment plants through FT-IR and TED-GC-MS - Jae-Ho Lee; Min-Jung Kim; Chang-Soo Kim; So-Jeong Cheon; Ki-In Choi; Juyang Kim; Jaehak Jung; Jeong-Ki Yoon; Soo-Hyung Lee; Dong-Hwan Jeong (Environmental Pollution, 2023)

Pectobacterium jejuense sp. nov. Isolated from Cucumber Stem Tissue - Soo-Min Hong; Leonid N. Ten; Kyoung-Taek Park; Chang-Gi Back; Malgorzata Waleron; In-Kyu Kang; Seung-Yeol Lee; Hee-Young Jung (Current Microbiology, 2023)

Disruption of type I interferon pathway and reduced production of IFN-α by parabens in virus-infected dendritic cells - In-Gu Lee; Yong-Hyun Joo; Hoyeon Jeon; Jung-Woong Kim; Young-Jin Seo; So-Hee Hong (Genes & Genomics, 2023)

Cold-induced adaptive thermogenesis is impaired by exposure of Asian sand dust in mice - Bernadette B. Bagon; Junhyeong Lee; Merc Emil Matienzo; Se-Jin Lee; So-Won Pak; Keon Kim; Jeongmin Lee; Chang-Min Lee; In-Sik Shin; Changjong Moon; Min-Jung Park; Dong-il Kim (Journal of Thermal Biology, 2023)

Evaluation of fermented soybean meal and edible insect hydrolysates as potential serum replacement in pig muscle stem cell culture - Cho Hyun Kim; Hyun Jung Lee; Doo Yeon Jung; Minsu Kim; Hyun Young Jung; Heesang Hong; Yun-Sang Choi; Hae In Yong; Cheorun Jo (Food Bioscience, 2023)

Coupling of δ13C and δ15N to understand soil organic matter sources and C and N cycling under different land-uses and management: a review and data analysis - Hyun-Jin Park; Nuri Baek; Sang-Sun Lim; Young-Jae Jeong; Bo-Seong Seo; Jin-Hyeob Kwak; Sang-Mo Lee; Seok-In Yun; Han-Yong Kim; Muhammad A. Arshad; Woo-Jung Choi (Biology and Fertility of Soils, 2023)

Unveiling reactive origin through the in situ 2D core–shell formation, Ni(CN)2@Ni2P, derived from Hofmann-type MOF for water oxidation - Jiwon Kim; Hyung Wook Choi; Jongseok Kim; Jung Hyeon Yoo; Dong In Jeong; Ui Young Lee; Hyuk Choi; Bong Kyun Kang; Ki-Seok An; Hyun You Kim; Dae Ho Yoon (Chemical Engineering Journal, 2023)

Bacterial Communities Associated with the Rhizosphere of Transgenic Chrysanthemum - In Soon Pack; Jin Ho Heo; Do Young Kim; Ho Jin Cho; Sung-Dug Oh; Seong-Kon Lee; Eun-Jung Suh; Chang-Gi Kim (Journal of Plant Biology, 2023)

Inverse opal-structured all-in-one water purification filter designed for the effective removal of multi-pollutants - Hee Jung Kim; Gill Sang Han; Jaesung Kim; Young Ju Kim; Jin Hyuk Choi; Jae Myeong Lee; Geon Woo Yoon; Hongshin Lee; In Sun Cho; Jaesang Lee; Hyun Suk Jung (Journal of Water Process Engineering, 2023)

Effects of edible insect extracts on the antioxidant, physiochemical, and microbial properties of Tteokgalbi during refrigerated storage - Hae In Yong; Tae-Kyung Kim; Ji Yoon Cha; Jae Hoon Lee; Min-Cheol Kang; Samooel Jung; Yun-Sang Choi (Food Bioscience, 2023)

Probabilistic analysis of rainfall-induced shallow landslide susceptibility using a physically based model and the bootstrap method - In-Tak Hwang; Hyuck-Jin Park; Jung-Hyun Lee (Landslides, 2023)

Understanding protein digestion in infants and the elderly: Current in vitro digestion models - Seonmin Lee; Kyung Jo; Hyun Gyung Jeong; Yun-Sang Choi; Hae In Yong; Samooel Jung (Critical Reviews in Food Science and Nutrition, 2023)

Characteristics of pork emulsion gel manufactured with hot-boned pork and winter mushroom powder without phosphate - Hyun Gyung Jeong; Kyung Jo; Seonmin Lee; Hae In Yong; Yun-Sang Choi; Samooel Jung (Meat Science, 2023)

Unraveling the mutualistic interaction between endophytic Curvularia lunata CSL1 and tomato to mitigate cadmium (Cd) toxicity via transcriptomic insights - Sajjad Asaf; Rahmatullah Jan; Muhammad Aaqil Khan; Lubna; Abdul Latif Khan; Saleem Asif; Saqib Bilal; Waqar Ahmad; Muhammad Waqas; Kyung-Min Kim; Ahmed AL-Harrasi; In-Jung Lee (Science of The Total Environment, 2023)

Melatonin alleviates arsenic (As) toxicity in rice plants via modulating antioxidant defense system and secondary metabolites and reducing oxidative stress - Rahmatullah Jan; Saleem Asif; Sajjad Asaf; Lubna; Xiao-Xuan Du; Jae-Ryoung Park; Kim Nari; Dibya Bhatta; In-jung Lee; Kyung-Min Kim (Environmental Pollution, 2023)

Microbial contribution to organic carbon accumulation in volcanic ash soils - Hye In Yang; Nuri Baek; Jin-Hyeob Kwak; Sang-Sun Lim; Young-Han Lee; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2023)

Tannic acid-assisted in-situ interfacial formation of Prussian blue-assembled adsorptive membranes for radioactive cesium removal - Sung-Joon Park; Seung Su Shin; Joon Hee Jo; Chan Hee Jung; Hosik Park; You-In Park; Hyung-Ju Kim; Jung-Hyun Lee (Journal of Hazardous Materials, 2023)

Efficacy of endophytic SB10 and glycine betaine duo in alleviating phytotoxic impact of combined heat and salinity in Glycine max L. via regulation of redox homeostasis and physiological and molecular responses - Saqib Bilal; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Ahmed Al-Harrasi; In-Jung Lee (Environmental Pollution, 2023)

In-situ preparation of gel polymer electrolytes in a fully-assembled lithium ion battery through deeply-penetrating high-energy electron beam irradiation - Seokyoung Park; Joon-Yong Sohn; In-Tae Hwang; Junhwa Shin; Jin-Mun Yun; KwangSup Eom; Kwanwoo Shin; Young-Moo Lee; Chan-Hee Jung (Chemical Engineering Journal, 2023)

3-Hydroxymorphinan protects against hypoxia-induced cell death in primary astrocyte by regulating Ca2+ influx and the glutamate homeostasis - Ok-Hyeon Kim; Gyeong Yun Lee; Kyung Yong Kim; Jong In Son; Tae Woo Jung; Ji Hoon Jeong; Joon Seok Bang; Hyoung-Chun Kim; Yoon Hee Chung; Hyun Jung Lee (Molecular & Cellular Toxicology, 2023)

Description of Microbacterium neungamense sp. nov. isolated from a hot spring - Dariimaa Ganbat; Ga Eul Jeong; DoKyung Oh; Dong-Woo Lee; Yong-Jik Lee; Seong-Bo Kim; In-Tae Cha; Won-Jae Chi; Seul-Ki Park; Jung-Sook Lee; Sang-Jae Lee (Archives of Microbiology, 2023)

Oculomics for sarcopenia prediction: a machine learning approach toward predictive, preventive, and personalized medicine - Bo Ram Kim; Tae Keun Yoo; Hong Kyu Kim; Ik Hee Ryu; Jin Kuk Kim; In Sik Lee; Jung Soo Kim; Dong-Hyeok Shin; Young-Sang Kim; Bom Taeck Kim (EPMA Journal, 2022)

Population genomics study for the conservation management of the endangered shrub Abeliophyllum distichum - Jung-Hoon Lee; Homervergel G. Ong; Bo-Yun Kim; Yong-In Kim; Eui-Kwon Jung; Myong Gi Chung; Young-Dong Kim (Conservation Genetics, 2022)
Natural monuments are IUCN Category III protected areas that play an important role in biodiversity conservation as they provide species refuge and allow species migration. Despite their status, natural monuments are often confined to cultural and fragmented landscapes due to anthropogenic land-use demands. In this population genomic study, we surveyed 11 populations of the endemic shrub Abeliophyllum distichum Nakai (Oleaceae), including five natural monument habitats, covering its range-wide distribution in South Korea. Using 2,254 SNPs as markers, our results showed a mean expected heterozygosity ( He ) of 0.319, with populations in the central distribution showing significantly higher He than those at the periphery. There was no significant heterozygote deficiency and inbreeding among studied populations overall ( F IS = −0.098), except for a single natural monument population (GS-NM147). Population structure and differentiation was moderate to high ( F ST = 0.196), while recent gene flow between populations appeared weak, which can be attributed to the fragmented distribution and the outcrossing mating system of the heterostylous plant. Based on these findings, we provide suggestions for the population conservation and management of this endangered species.

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

Immobilization of Laccase Through Inorganic-Protein Hybrids Using Various Metal Ions - Sanjay K. S. Patel; Vipin C. Kalia; Sang-Yong Kim; Jung-Kul Lee; In-Won Kim (Indian Journal of Microbiology, 2022)

Land use types with different fertilization management affected isotope ratios of bulk and water-extractable C and N of soils in an intensive agricultural area - Young-Jae Jeong; Hyun-Jin Park; Byeong-Jun Jeon; Bo-Seong Seo; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2022)

Electron transport and photosynthetic performance in Fragaria × ananassa Duch. acclimated to the solar spectrum modified by a spectrum conversion film - Jun Hyeun Kang; Hyo In Yoon; Jae Moon Lee; Jae Pil Kim; Jung Eek Son (Photosynthesis Research, 2022)

Biomolecules Production from Greenhouse Gases by Methanotrophs - Sanjay K. S. Patel; Ramsamy Shanmugam; Jung-Kul Lee; Vipin C. Kalia; In-Won Kim (Indian Journal of Microbiology, 2021)

Synergistic interaction of fungal endophytes, Paecilomyces formosus LHL10 and Penicillium funiculosum LHL06, in alleviating multi-metal toxicity stress in Glycine max L. - Saqib Bilal; Raheem Shahzad; In-Jung Lee (Environmental Science and Pollution Research, 2021)

Anti-inflammatory activity of palmitoylethanolamide ameliorates osteoarthritis induced by monosodium iodoacetate in Sprague–Dawley rats - Jae In Jung; Hyun Sook Lee; Young Eun Jeon; So Mi Kim; Su Hee Hong; Joo Myung Moon; Cho Young Lim; Yoon Hee Kim; Eun Ji Kim (Inflammopharmacology, 2021)
Novel treatment strategies are urgently required for osteoarthritis (OA). Palmitoylethanolamide (PEA) is a naturally occurring fatty acid amide with analgesic and anti-inflammatory effects. We aimed to examine its effect on OA and elucidate the molecular mechanism of actions in monosodium iodoacetate (MIA)-induced OA Sprague–Dawley rats. The experimental animals were divided into normal control group (injected with saline + treated with phosphate-buffered saline (PBS), NOR), control group (injected with MIA + treated with PBS, CON), 50 or 100 mg/kg body weight (BW)/day PEA-treated group (injected with MIA + treated with 50 or 100 mg of PEA/kg BW/day, PEA50 or PEA100), and positive control group (injected with MIA + treated with 6 mg of diclofenac/kg BW/day, DiC). The changes in blood parameters, body parameters, gene expression of inflammatory mediators and cytokines, knee thickness, and joint tissue were observed. Oral administration of PEA had no adverse effects on the BW, liver, or kidneys. PEA reduced knee joint swelling and cartilage degradation in MIA-induced OA rats. The serum levels of leukotriene B4, nitric oxide, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and prostaglandin E2 considerably reduced in the PEA100 group compared with those in the CON group. In the synovia of knee joints, the mRNA expression of iNOS , 5-Lox , Cox-2 , Il-1β , Tnf-α , and Mmp-2 , -3 , -9 , and -13 apparently increased with MIA administration. Meanwhile, Timp-1 mRNA expression apparently decreased in the CON group but increased to the normal level with PEA treatment. Thus, PEA can be an effective therapeutic agent for OA.

Lactucin induces apoptosis through reactive oxygen species-mediated BCL-2 and CFLARL downregulation in Caki-1 cells - Ji Hoon Jang; Cho-Young Park; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Chuleui Jung; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2021)

Biotin and Zn2+ Increase Xylitol Production by Candida tropicalis - Gurusamy Muneeswaran; Sanjay K. S. Patel; Sanath Kondaveeti; Ramasamy Shanmugam; Krishnasamy Gopinath; Virendra Kumar; Sang-Yong Kim; Jung-Kul Lee; Vipin Chandra Kalia; In-Won Kim (Indian Journal of Microbiology, 2021)

Orphan nuclear receptor ERRγ regulates hepatic TGF-β2 expression and fibrogenic response in CCl4-induced acute liver injury - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina Kim; In-Kyu Lee; Sung Jin Cho; Don-Kyu Kim; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2021)

Adhaeribacter terrigena sp. nov., Isolated from Korean Soil - Leonid N. Ten; Weilan Li; Myung Kyum Kim; In‑Kyu Kang; Seung-Yeol Lee; Hee-Young Jung (Current Microbiology, 2021)

Transcriptome analysis of primary chicken cells infected with infectious bronchitis virus strain K047-12 isolated in Korea - Rangyeon Lee; Ji Seung Jung; Ji-in Yeo; Hyuk Moo Kwon; Jeongho Park (Archives of Virology, 2021)

Temporal variation of sulfate concentration in PM2.5 and major factors enhancing sulfate concentration in the atmosphere of Seoul, Korea - Na Kyung Kim; In Sun Kim; In Ho Song; Seung Myung Park; Hyung Bae Lim; Yong Pyo Kim; Hye Jung Shin; Ji Yi Lee (Air Quality, Atmosphere & Health, 2021)

Mucilaginibacter segetis sp. nov., Isolated from Soil - Weilan Li; Leonid N. Ten; Myung Kyum Kim; Seung-Yeol Lee; In‑Kyu Kang; Hee-Young Jung (Current Microbiology, 2021)

Source identification and assessment of heavy metal contamination in urban soils based on cluster analysis and multiple pollution indices - Hong-gil Lee; Hyun-Koo Kim; Hoe-Jung Noh; Yoon Joo Byun; Hyen-Mi Chung; Ji-In Kim (Journal of Soils and Sediments, 2021)

Rhus vernicifera Laccase Immobilization on Magnetic Nanoparticles to Improve Stability and Its Potential Application in Bisphenol A Degradation - Sanjay K. S. Patel; Rahul K. Gupta; Sang-Yong Kim; In-Won Kim; Vipin C. Kalia; Jung-Kul Lee (Indian Journal of Microbiology, 2021)

Hymenobacter busanensis sp. nov., radiation-resistant species isolated from soil in South Korea - Sang Eun Lee; Leonid N. Ten; Yuna Park; Soohyun Maeng; Jing Zhang; Min-Kyu Kim; In-Tae Cha; Ki-Eun Lee; Byoung-Hee Lee; Hee ‑ Young Jung; Myung Kyum Kim (Archives of Microbiology, 2021)

N-type Cav channel inhibition by spider venom peptide of Argiope bruennichi - In-Wook Hwang; Min Kyoung Shin; Yoo-Jung Lee; Seung Tae Kim; Sue Yeon Lee; Byungjo Lee; Wonhee Jang; Joo-Hong Yeo; Seungki Lee; Jung-Suk Sung (Molecular & Cellular Toxicology, 2021)

Modulation of sugar and nitrogen in callus induction media alter PAL pathway, SA and biomass accumulation in rice callus - Rahmatullah Jan; Muhammad Aaqil Khan; Sajjad Asaf; In-Jung Lee; Kyung-Min Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Metformin ameliorates animal models of dermatitis - Soo Young Choi; Chanmi Lee; Min-Jeong Heo; Yeong Min Choi; In-sook An; Seunghee Bae; Sungkwan An; Jin Hyuk Jung (Inflammopharmacology, 2020)

Biomass, chemical composition, and microbial decomposability of rice root and straw produced under co-elevated CO2 and temperature - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Kwang-Seung Lee; Hye In Yang; Han-Yong Kim; Sang-Mo Lee; Woo-Jung Choi (Biology and Fertility of Soils, 2020)

High-throughput phenotyping platform for analyzing drought tolerance in rice - Song Lim Kim; Nyunhee Kim; Hongseok Lee; Eungyeong Lee; Kyeong-Seong Cheon; Minsu Kim; JeongHo Baek; Inchan Choi; Hyeonso Ji; In Sun Yoon; Ki-Hong Jung; Taek-Ryoun Kwon; et al. (Planta, 2020)
Main conclusion A new imaging platform was constructed to analyze drought-tolerant traits of rice. Rice was used to quantify drought phenotypes through image-based parameters and analyzing tools. Abstract Climate change has increased the frequency and severity of drought, which limits crop production worldwide. Developing new cultivars with increased drought tolerance and short breeding cycles is critical. However, achieving this goal requires phenotyping a large number of breeding populations in a short time and in an accurate manner. Novel cutting-edge technologies such as those based on remote sensors are being applied to solve this problem. In this study, new technologies were applied to obtain and analyze imaging data and establish efficient screening platforms for drought tolerance in rice using the drought-tolerant mutant osphyb . Red–Green–Blue images were used to predict plant area, color, and compactness. Near-infrared imaging was used to determine the water content of rice, infrared was used to assess plant temperature, and fluorescence was used to examine photosynthesis efficiency. DroughtSpotter technology was used to determine water use efficiency, plant water loss rate, and transpiration rate. The results indicate that these methods can detect the difference between tolerant and susceptible plants, suggesting their value as high-throughput phenotyping methods for short breeding cycles as well as for functional genetic studies of tolerance to drought stress.

Land-use type, and land management and disturbance affect soil δ15N: a review - Woo-Jung Choi; Jin-Hyeob Kwak; Hyun-Jin Park; Hye In Yang; Se-In Park; Zhihong Xu; Sang-Mo Lee; Sang-Sun Lim; Scott X. Chang (Journal of Soils and Sediments, 2020)

Strong alkaline condition is preferable for producing 7,10-dihydroxy-8(E)-hexadecenoic acid from palmitoleic acid by Pseudomonas aeruginosa KNU-2B - Ji-Sun Moon; Yeon-Jung Lee; In-Hwan Kim; Hak-Ryul Kim (Biotechnology Letters, 2020)

De novo assembly and characterization of transcriptome in the medicinal plant Euphorbia jolkini - Neha Samir Roy; In-hye Lee; Jung-A Kim; Rahul Vasudeo Ramekar; Kyong-Cheul Park; Nam-il Park; Joo-Hong Yeo; Ik-Young Choi; Soonok Kim (Genes & Genomics, 2020)

Production of 7,10,12-trihydroxy-8(E)-octadecenoic acid from ricinoleic acid by Pseudomonas aeruginosa KNU-2B - Yeon-Jung Lee; Ji-Sun Moon; In-Hwan Kim; Hak-Ryul Kim (Biotechnology Letters, 2020)

Characterization of Cellobiohydrolases from Schizophyllum commune KMJ820 - Sanath Kondaveeti; Sanjay K. S. Patel; Janghun Woo; Ji Hyang Wee; Sang-Yong Kim; Riyadh I. Al-Raoush; In-Won Kim; Vipin Chandra Kalia; Jung-Kul Lee (Indian Journal of Microbiology, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

Streptomyces sp. LH 4 promotes plant growth and resistance against Sclerotinia sclerotiorum in cucumber via modulation of enzymatic and defense pathways - Bong-Gyu Mun; Won-Hee Lee; Sang-Mo Kang; Sang-Uk Lee; Seok-Min Lee; Dong Yeol Lee; Muhammad Shahid; Byung-Wook Yun; In-Jung Lee (Plant and Soil, 2020)

Histone deacetylase inhibitor CG200745 ameliorates high-fat diet-induced hypertension via inhibition of angiotensin II production - Ga-Eun Yoon; Jin Ki Jung; Yun-Han Lee; Byeong-Churl Jang; Jee In Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)
Obesity is growing rapidly worldwide due to consumption of westernized diet and lack of exercise. Obesity is one of the major risk factors of hypertension. The novel histone deacetylase (HDAC) inhibitor CG200745 was originally developed to treat various cancers. Previous studies showed that CG200745 attenuated hypertension through inhibition of cardiac hypertrophy and fibrosis in deoxycorticosterone acetate-induced hypertensive rat. The purpose of this study is to investigate the role and underlying mechanism of CG200745 in high-fat diet (HFD)-induced hypertension. Nine-week old C57BL/6 mice were fed a normal diet (ND) or HFD for 17 weeks. Each group of mice was treated with vehicle or CG200745 by intraperitoneal injection for 9 days. HFD group showed higher body weight, blood pressure (BP), HDAC activities, angiotensinogen and renin expressions in kidney, angiotensin-converting enzyme (ACE) expression in the lung, serum angiotensin II (Ang II) concentration, and myosin light chain 20 (MLC 20 ) phosphorylation in mesenteric artery compared with ND group. CG200745 lowered BP, HDAC activity, renin and angiotensinogen in the kidney, ACE in the lung, serum Ang II level, and phosphorylation of MLC 20 in HFD group. In conclusion, CG200745 ameliorated HFD-induced hypertension through inhibition of HDAC/Ang II/vascular contraction axis. Our results offer CG200745 as a novel therapeutic option for HFD-induced hypertension.

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Implantable electrical stimulation bioreactor with liquid crystal polymer-based electrodes for enhanced bone regeneration at mandibular large defects in rabbit - Chaebin Kim; Hoon Joo Yang; Tae Hyung Cho; Beom Seok Lee; Tae Mok Gwon; Soowon Shin; In Sook Kim; Sung June Kim; Soon Jung Hwang (Medical & Biological Engineering & Computing, 2020)

An inverse agonist of estrogen-related receptor γ regulates 2-arachidonoylglycerol synthesis by modulating diacylglycerol lipase expression in alcohol-intoxicated mice - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina kim; Don-Kyu Kim; Ji-Hyeok Lee; Hyunhee Oh; In-Kyu Lee; Wook Kim; Sung Jin Cho; Cheol Soo Choi; Steven Dooley; et al. (Archives of Toxicology, 2020)

Hepatocyte CREBH deficiency aggravates inflammatory liver injury following chemokine-dependent neutrophil infiltration through upregulation of NF-κB p65 in mice - Jung-Ran Noh; Jae-Hoon Kim; Soon-Young Na; In Bok Lee; Yun Jeong Seo; Jung Hyeon Choi; Youngwon Seo; Tae Geol Lee; Hueng-Sik Choi; Yong-Hoon Kim; Chul-Ho Lee (Archives of Toxicology, 2020)

Analysis of Determinants for an Enhanced and Long-lasting Coastal Convective System by Means of a Case Study (26 July 2011) - Jung-Tae Lee; Dong-In Lee; Shingo Shimizu; Cheol-Hwan You (Advances in Atmospheric Sciences, 2019)

In Situ Gelling Hydrogel with Anti-Bacterial Activity and Bone Healing Property for Treatment of Osteomyelitis - Sun Woo Jung; Se Heang Oh; In Soo Lee; June-Ho Byun; Jin Ho Lee (Tissue Engineering and Regenerative Medicine, 2019)

Antimicrobial Activity of Biosynthesized Silver Nanoparticles Decorated Silica Nanoparticles - Sachin V. Otari; Sanjay K. S. Patel; Vipin C. Kalia; In-Won Kim; Jung-Kul Lee (Indian Journal of Microbiology, 2019)

Multidrug-resistant Acinetobacter baumannii infection in lung transplant recipients: risk factors and prognosis - Dong Hyun Oh; Yong Chan Kim; Eun Jin Kim; In Young Jung; Su Jin Jeong; Song Yee Kim; Moo Suk Park; Anes Kim; Jin Gu Lee; Hyo Chae Paik (Infectious Diseases, 2019)

Prevention and relaxation effects of Liriope platyphylla on bronchial asthma in vitro model by suppressing the activities of MAPK/NF-κB pathway - In-Seung Lee; Dong-Hyun Kim; Kang-Hoon Kim; Jiyoung Park; Yumi Kim; Eun-Jin An; Kwanil Kim; Hee-Jae Jung; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2019)

Cloning, Expression and Characterization of a Highly Active Alcohol Dehydrogenase for Production of Ethyl (S)-4-Chloro-3-Hydroxybutyrate - Yi-Hao Zhu; Cai-Yun Liu; Sha Cai; Li-Bin Guo; In-Won Kim; Vipin C. Kalia; Jung-Kul Lee; Ye-Wang Zhang (Indian Journal of Microbiology, 2019)

Elevated carbon dioxide significantly improves ascorbic acid content, antioxidative properties and restricted biomass production in cruciferous vegetable seedlings - Muthusamy Muthusamy; Jung Eun Hwang; Suk Hee Kim; Jin A. Kim; Mi-Jeong Jeong; Hyeong Cheol Park; Soo In Lee (Plant Biotechnology Reports, 2019)

Trpm2 Ablation Accelerates Protein Aggregation by Impaired ADPR and Autophagic Clearance in the Brain - Yongwoo Jang; Byeongjun Lee; Hyungsup Kim; Seungmoon Jung; Sung Hoon Lee; So-Young Lee; Ji Hyun Jeon; In-Beom Kim; Seo-Ho Lee; Byung-Ju Kim; Uh-Hyun Kim; Yunjong Lee; et al. (Molecular Neurobiology, 2019)

PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2019)
Impaired neurogenesis has been associated with several brain disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The role of peroxiredoxin 6 (PRDX6) in neurodegenerative diseases is very controversial. To demonstrate the role of PRDX6 in neurogenesis, we compared the neurogenesis ability of PRDX6-overexpressing transgenic (Tg) mice and wild-type mice and studied the involved molecular mechanisms. We showed that the neurogenesis of neural stem cells (NSCs) and the expression of the marker protein were lower in PRDX6 Tg-mice than in wild-type mice. To determine the factors involved in PRDX6-related neural stem cell impairment, we performed a microarray experiment. We showed that the expression of WDFY1 was dramatically decreased in PRDX6-Tg mice. Moreover, WDFY1 siRNA decreases the differentiation ability of primary neural stem cells. Interestingly, WDFY1 reportedly recruits the signaling adaptor TIR-domain-containing adapter-inducing interferon-β (TRIF) to toll-like receptors (TLRs); thus, we showed the relationship among TLRs, PRDX6, and WDFY1. We showed that TLR4 was dramatically reduced in PRDX6 Tg mice, and reduced TLR4 expression and neurogenesis was reversed by the introduction of WDFY1 plasmid in the neural stem cells from PRDX6 Tg mice. This study indicated that PRDX6 inhibits the neurogenesis of neural precursor cells through TLR4-dependent downregulation of WDFY1 and suggested that the inhibitory effect of PRDX6 on neurogenesis play a role in the development of neurodegenerative diseases in the PRDX6 overexpressing transgenic mice.

Repositioning of the antipsychotic drug TFP for sepsis treatment - Jung Hwa Park; Hyun Jin Park; Sung Eun Lee; Young Seob Kim; Gun-Young Jang; Hee Dong Han; In Duk Jung; Kyung Chul Shin; Young Min Bae; Tae Heung Kang; Yeong-Min Park (Journal of Molecular Medicine, 2019)

Growth-promoting bioactivities of Bipolaris sp. CSL-1 isolated from Cannabis sativa suggest a distinctive role in modifying host plant phenotypic plasticity and functions - Lubna; Sajjad Asaf; Abdul Latif Khan; Muhammad Waqas; Sang-Mo Kang; Muhammad Hamayun; In-Jung Lee; Anwar Hussain (Acta Physiologiae Plantarum, 2019)

Stem Cells Seeded on Multilayered Scaffolds Implanted into an Injured Bladder Rat Model Improves Bladder Function - Kshitiz Raj Shrestha; Seung Hwan Jeon; Ae Ryang Jung; In Gul Kim; Ga Eun Kim; Yong Hyun Park; Soo Hyun Kim; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Bioelectrogenesis from Raw Algal Biomass Through Microbial Fuel Cells: Effect of Acetate as Co-substrate - Sanath Kondaveeti; Gunda Mohanakrishna; Raviteja Pagolu; In-Won Kim; Vipin C. Kalia; Jung-Kul Lee (Indian Journal of Microbiology, 2019)

Copper Ferrite Magnetic Nanoparticles for the Immobilization of Enzyme - Sachin V. Otari; Sanjay K. S. Patel; Sang-Yong Kim; Jung Rim Haw; Vipin C. Kalia; In-Won Kim; Jung-Kul Lee (Indian Journal of Microbiology, 2019)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)

Improvement of blood culture contamination rate, blood volume, and true positive rate after introducing a dedicated phlebotomy team - Moonsuk Bae; Hae In Kim; Joung Ha Park; Byung-Han Ryu; Jeonghyun Chang; Heungsup Sung; Jiwon Jung; Min Jae Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Severe Cardiomyopathy Due to Arthroprosthetic Cobaltism: Report of Two Cases with Different Outcomes - Hyo-In Choi; Jung Ae Hong; Min-Seok Kim; Sang Eun Lee; Sung-Ho Jung; Pil Whan Yoon; Joon Seon Song; Jae-Joong Kim (Cardiovascular Toxicology, 2019)

Sorption of Pb in chemical and particle-size fractions of soils with different physico-chemical properties - Hyun-Jung Park; Hyun-Jin Park; Hye In Yang; Se-In Park; Sang-Sun Lim; Jin-Hyeob Kwak; Goon-Taek Lee; Sang-Mo Lee; Man Park; Woo-Jung Choi (Journal of Soils and Sediments, 2019)

Inoculum effect of methicillin-susceptible Staphylococcus aureus against broad-spectrum beta-lactam antibiotics - Kyoung-Ho Song; Sook-In Jung; Shinwon Lee; Sohee Park; Eu Suk Kim; Kyung-Hwa Park; Wan Beom Park; Pyoeng Gyun Choe; Young Keun Kim; Yee Gyung Kwak; Yeon-Sook Kim; Hee-Chang Jang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Hymenobacter pomorum sp. nov., Isolated from Apple Orchard Soil - Leonid N. Ten; Weilan Li; Seung-Yeol Lee; In-Kyu Kang; Young-Je Cho; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2019)

Halo-tolerant rhizospheric Arthrobacter woluwensis AK1 mitigates salt stress and induces physio-hormonal changes and expression of GmST1 and GmLAX3 in soybean - Muhammad Aaqil Khan; Ihsan Ullah; Muhammad Waqas; Muhammad Hamayun; Abdul Latif Khan; Sajjad Asaf; Sang-Mo Kang; Kyung-Min Kim; Rahmatullah Jan; In-Jung Lee (Symbiosis, 2019)

First reported chloroplast genome sequence of Punica granatum (cultivar Helow) from Jabal Al-Akhdar, Oman: phylogenetic comparative assortment with Lagerstroemia - Abdul Latif Khan; Sajjad Asaf; In-Jung Lee; Ahmed Al-Harrasi; Ahmed Al-Rawahi (Genetica, 2018)

Endophytic fungus Paecilomyces formosus LHL10 produces sester-terpenoid YW3548 and cyclic peptide that inhibit urease and α-glucosidase enzyme activities - Saqib Bilal; Liaqat Ali; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Sang-Mo Kang; Sang-Kuk Kim; In-Jung Lee (Archives of Microbiology, 2018)

Flavobacterium knui sp. nov., a novel member of the family Flavobacteriaceae - Seo-Yeong Kim; Leonid N. Ten; Seung-Yeol Lee; Seung-Han Kim; In-Kyu Kang; Hee-Young Jung (Antonie van Leeuwenhoek, 2018)

Effects of CYP2C19 and CYP3A5 genetic polymorphisms on the pharmacokinetics of cilostazol and its active metabolites - Hye-In Lee; Ji-Young Byeon; Young-Hoon Kim; Choong-Min Lee; Chang-Ik Choi; Choon-Gon Jang; Jung-Woo Bae; Yun Jeong Lee; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2018)

Plant growth promoting endophytic fungi Asprgillus fumigatus TS1 and Fusarium proliferatum BRL1 produce gibberellins and regulates plant endogenous hormones - Lubna Bilal; Sajjad Asaf; Muhammad Hamayun; Humaira Gul; Amjad Iqbal; Ihsan Ullah; In-Jung Lee; Anwar Hussain (Symbiosis, 2018)

Functional conservation of Arabidopsis LNG1 in tobacco relating to leaf shape change by increasing longitudinal cell elongation by overexpression - Young Koung Lee; In-Jung Kim (Genes & Genomics, 2018)

Hymenobacter agri sp. nov., a novel bacterium isolated from soil - Jigon Han; Leonid N. Ten; Dong Hoon Lee; In-Kyu Kang; Hee-Young Jung (Antonie van Leeuwenhoek, 2018)

Recent Primary Production and Small Phytoplankton Contribution in the Yellow Sea during the Summer in 2016 - Hyo Keun Jang; Jae Jung Kang; Jae Hyung Lee; Myungjoon Kim; So Hyun Ahn; Jin-Yong Jeong; Mi Sun Yun; In-Seong Han; Sang Heon Lee (Ocean Science Journal, 2018)

Phenylethanoid glycoside from Forsythia koreana (Oleaceae) flowers shows a neuroprotective effect - Yeong-Geun Lee; Kyeong-Hwa Seo; Dong-Sung Lee; Jung Eun Gwag; Hyoung-Geun Kim; Jung-Hwan Ko; So-Hyun Park; Dae Young Lee; In Ho Jung; Nam-In Baek (Brazilian Journal of Botany, 2018)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Inverse agonist of ERRγ reduces cannabinoid receptor type 1-mediated induction of fibrinogen synthesis in mice with a high-fat diet-intoxicated liver - Yaochen Zhang; Don-Kyu Kim; Yoon Seok Jung; Yong-Hoon Kim; Yong Soo Lee; Jina Kim; Won-IL Jeong; In-Kyu Lee; Sung Jin Cho; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2018)

Elevated CO2 concentration affected pine and oak litter chemistry and the respiration and microbial biomass of soils amended with these litters - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Hye-In Yang; Kwang-Seung Lee; Young-Han Lee; Han-Yong Kim; Woo-Jung Choi (Biology and Fertility of Soils, 2018)

Gender affects prognosis of methicillin-resistant Staphylococcus aureus bacteremia differently depending on the severity of underlying disease - Chang Kyung Kang; Yee Gyung Kwak; Youngmi Park; Kyoung-Ho Song; Eu Suk Kim; Sook-In Jung; Kyung-Hwa Park; Wan Beom Park; Nam Joong Kim; Young Keun Kim; Hee-Chang Jang; Shinwon Lee; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Spirosoma agri sp. nov., Isolated from Apple Orchard Soil - Weilan Li; Seung-Yeol Lee; In-Kyu Kang; Leonid N. Ten; Hee-Young Jung (Current Microbiology, 2018)

Genetic variability comparison of cultured Israeli carp (Cyprinus carpio) from Korea using microsatellites - Jung Eun Kim; In Bon Goo; Ju-ae Hwang; Hyeong Su Kim; Hye-Sung Choi; Jeong-Ho Lee (Genes & Genomics, 2018)

Real Data Assimilation Using the Local Ensemble Transform Kalman Filter (LETKF) System for a Global Non-hydrostatic NWP model on the Cubed-sphere - Seoleun Shin; Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Kwangjae Sung; Kyoungmi Cho; Youngsoon Jo; Jung-Eun Kim; In-Hyuk Kwon; Sujeong Lim; Ji-Sun Kang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

The Korean Integrated Model (KIM) System for Global Weather Forecasting - Song-You Hong; Young Cheol Kwon; Tae-Hun Kim; Jung-Eun Esther Kim; Suk-Jin Choi; In-Hyuk Kwon; Junghan Kim; Eun-Hee Lee; Rae-Seol Park; Dong-Il Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Regulation of endogenous phytohormones and essential metabolites in frankincense-producing Boswellia sacra under wounding stress - Abdul Latif Khan; Ahmed Al-Harrasi; Raheem Shahzad; Qari Muhammad Imran; Byung-Wook Yun; Yoon-Ha Kim; Sang-Mo Kang; Ahmed Al-Rawahi; In-Jung Lee (Acta Physiologiae Plantarum, 2018)

Fisetin protects H9c2 cardiomyoblast cells against H2O2-induced apoptosis through Akt and ERK1/2 signaling pathways - Jeong Soo Lee; Ji-Sook Lee; Kyung Jae Cha; Dae-Eun Kim; Daye Lee; Sun Young Jung; Eun-Seok Park; In Sik Kim (Molecular & Cellular Toxicology, 2018)

Spirosoma terrae sp. nov., Isolated from Soil from Jeju Island, Korea - Leonid N. Ten; Joseph Okiria; Jae-Jin Lee; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2018)

Synthesis of Protein-Inorganic Nanohybrids with Improved Catalytic Properties Using Co3(PO4)2 - Ashok Kumar; In-Won Kim; Sanjay K. S. Patel; Jung-Kul Lee (Indian Journal of Microbiology, 2018)

Effects of 1-methylcyclopropene (1-MCP) and polyethylene (PE) film liner treatments on the fruit quality of cold-stored ‘Gamhong’ apples - Kyoung-ook Kim; Jingi Yoo; Jinwook Lee; Nay Myo Win; Seulgi Ryu; Jeung-Sul Han; Hee-Young Jung; Myoung-Gun Choung; Yong-Deuk Kwon; Dong Hoon Lee; In-Kyu Kang (Horticulture, Environment, and Biotechnology, 2018)

Development of RNA aptamer that inhibits methyltransferase activity of dengue virus - Jae In Jung; Seung Ryul Han; Seong-Wook Lee (Biotechnology Letters, 2018)

IAA-producing Klebsiella variicola AY13 reprograms soybean growth during flooding stress - Ah-Young Kim; Raheem Shahzad; Sang-Mo Kang; Chang-Woo Seo; Yeon-Gyeong Park; Hyun-Jin Park; In-Jung Lee (Journal of Crop Science and Biotechnology, 2017)

Foliar Treatment of Bacillus Methylotrophicus KE2 Reprograms Endogenous Functional Chemicals in Sesame to Improve Plant Health - Ramalingam Radhakrishnan; In-Jung Lee (Indian Journal of Microbiology, 2017)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Growth performance, oxidative stress, and non-specific immune responses in juvenile sablefish, Anoplopoma fimbria, by changes of water temperature and salinity - Jun-Hwan Kim; Hee-Ju Park; Kyeong-Wook Kim; In-Ki Hwang; Do-Hyung Kim; Chul Woong Oh; Jung Sick Lee; Ju-Chan Kang (Fish Physiology and Biochemistry, 2017)

Ssanghwa-Tang, a traditional herbal formula, suppresses cigarette smoke-induced airway inflammation via inhibition of MMP-9 and Erk signaling - Je-Won Ko; Na-Rae Shin; Sung-Hyeuk Park; In-Chul Lee; Jung-Min Ryu; Young-Kwon Cho; Jong-Choon Kim; Chang-Seob Seo; In-Sik Shin (Molecular & Cellular Toxicology, 2017)

Plant growth promoting effect of Bacillus amyloliquefaciens H-2-5 on crop plants and influence on physiological changes in soybean under soil salinity - Min-Ji Kim; Ramalingam Radhakrishnan; Sang-Mo Kang; Young-Hyun You; Eun-Ju Jeong; Jong-Guk Kim; In-Jung Lee (Physiology and Molecular Biology of Plants, 2017)

Erratum to: Hymenobacter knuensis sp. nov., Isolated From River Water - Leonid N. Ten; Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2017)

Hymenobacter knuensis sp. nov., Isolated From River Water - Leonid N. Ten; Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2017)

Overexpression of chloroplast-localized NADPH-dependent thioredoxin reductase C (NTRC) enhances tolerance to photo-oxidative and drought stresses in Arabidopsis thaliana - Mi Ri Kim; Laila Khaleda; In Jung Jung; Joo Yeon Kim; Sang Yeol Lee; Joon-Yung Cha; Woe-Yeon Kim (Journal of Plant Biology, 2017)

Deinococcus knuensis sp. nov., a bacterium isolated from river water - Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Leonid N. Ten; Hee-Young Jung (Antonie van Leeuwenhoek, 2017)

Endophytes from medicinal plants and their potential for producing indole acetic acid, improving seed germination and mitigating oxidative stress - Abdul Latif Khan; Syed Abdullah Gilani; Muhammad Waqas; Khadija Al-Hosni; Salima Al-Khiziri; Yoon-Ha Kim; Liaqat Ali; Sang-Mo Kang; Sajjad Asaf; Raheem Shahzad; Javid Hussain; In-Jung Lee; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Additive effects due to biochar and endophyte application enable soybean to enhance nutrient uptake and modulate nutritional parameters - Muhammad Waqas; Yoon-Ha Kim; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Hamayun; Sang-Mo Kang; Muhammad Aaqil Khan; In-Jung Lee (Journal of Zhejiang University-SCIENCE B, 2017)

Chloroform induces cystein-rich 61, a mediator of collagen homeostasis via early growth response-1 dependent pathway in human skin dermal fibroblasts - Hana Lee; Jae Beom Park; Woo-In Ryu; Ji Hyun Kim; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Geophysical evidence and inferred triggering factors of submarine landslides on the western continental margin of the Ulleung Basin, East Sea - Deniz Cukur; Seong-Pil Kim; Gee-Soo Kong; Jang-Jun Bahk; Senay Horozal; In-Kwon Um; Gwang-Soo Lee; Tae-Soo Chang; Hun-Jun Ha; David Völker; Jung-Ki Kim (Geo-Marine Letters, 2016)

Resistance to pathologic cardiac hypertrophy and reduced expression of CaV1.2 in Trpc3-depleted mice - Jung Woo Han; Young Ho Lee; Su-In Yoen; Joel Abramowitz; Lutz Birnbaumer; Min Goo Lee; Joo Young Kim (Molecular and Cellular Biochemistry, 2016)

Genetic characteristics of highly pathogenic H5N8 avian influenza viruses isolated from migratory wild birds in South Korea during 2014-2015 - Young-Jae Si; Won Suk Choi; Young-Il Kim; In-Won Lee; Hyeok-Il Kwon; Su-Jin Park; Eun-Ha Kim; Se mi Kim; Jin-Jung Kwon; Min-Suk Song; Chul-Joong Kim; Young-Ki Choi (Archives of Virology, 2016)

Reduction of GIGANTEA expression in transgenic Brassica rapa enhances salt tolerance - Jin A. Kim; Ha-eun Jung; Joon Ki Hong; Victor Hermand; C. Robertson McClung; Yeon-Hee Lee; Joo Yeol Kim; Soo In Lee; Mi-Jeong Jeong; Jungsun Kim; DaeJin Yun; WeoYeon Kim (Plant Cell Reports, 2016)

Toluene induces early growth response-1 dependent thymic stromal lymphopoietin expression in human keratinocytes - Hana Lee; Jae Beom Park; Hyu Cheol Bae; Woo-In Ryu; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Directing human embryonic stem cells towards functional endothelial cells easily and without purification - Chang-Hyun Gil; Byeong-Seong Ki; Joseph Seo; Jong-Jin Choi; Hana Kim; In-Gul Kim; A.-Ra Jung; Won-Young Lee; Youngsok Choi; Kwideok Park; Sung-Hwan Moon; Hyung-Min Chung (Tissue Engineering and Regenerative Medicine, 2016)

No association of CLOCK 3111T/C polymorphism with diurnal preference and sleep quality in Korean adults - Seong Jae Kim; Jung Hie Lee; Se Yong Lee; Jun-Won Hwang; In Bum Suh (Sleep and Biological Rhythms, 2016)

Phentermine induces conditioned rewarding effects via activation of the PI3K/Akt signaling pathway in the nucleus accumbens - Sa-Ik Hong; Min-Jung Kim; In-Jee You; Seung-Hwan Kwon; Shi-Xun Ma; Ji-Young Hwang; Jee-Yeon Seo; Yong-Hyun Ko; Bo Ram Lee; Seok-Yong Lee; Choon-Gon Jang (Psychopharmacology, 2016)

Bee Venom Acupuncture Alleviates Experimental Autoimmune Encephalomyelitis by Upregulating Regulatory T Cells and Suppressing Th1 and Th17 Responses - Min Jung Lee; Minhee Jang; Jonghee Choi; Gihyun Lee; Hyun Jung Min; Won-Seok Chung; Jong-In Kim; Youngheun Jee; Younbyoung Chae; Sung-Hoon Kim; Sung Joong Lee; Ik-Hyun Cho (Molecular Neurobiology, 2016)

Mycobacterium avium MAV2052 protein induces apoptosis in murine macrophage cells through Toll-like receptor 4 - Kang-In Lee; Han-Gyu Choi; Yeo-Jin Son; Jake Whang; Kwangwook Kim; Heat Sal Jeon; Hye-Soo Park; Yong Woo Back; Seunga Choi; Seong-Woo Kim; Chul Hee Choi; Hwa-Jung Kim (Apoptosis, 2016)

Spatial and diurnal variations of storm heights in the East Asia summer monsoon: storm height regimes and large-scale diurnal modulation - Myung-Sook Park; Myong-In Lee; Hyerim Kim; Jungho Im; Jung-Moon Yoo (Climate Dynamics, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

Bladder reconstruction using stem cells seeded on multilayered scaffolds in a mucosa preserving partial cystectomy model - Kshitiz Raj Shrestha; Yong Hyun Park; Yong Sun Choi; In Gul Kim; Shuyu Piao; Ae Ryang Jung; Seung Hwan Jeon; Se Heang Oh; Jin Ho Lee; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2015)

Mutualistic fungal endophytes produce phytohormones and organic acids that promote japonica rice plant growth under prolonged heat stress - Muhammad Waqas; Abdul Latif Khan; Raheem Shahzad; Ihsan Ullah; Abdur Rahim Khan; In-Jung Lee (Journal of Zhejiang University-SCIENCE B, 2015)

Shoot elongation and gibberellin contents in Cyclamen persicum are influenced by temperature and light intensity - Wook Oh; Jiseon Kim; Yoon Ha Kim; In-Jung Lee; Ki Sun Kim (Horticulture, Environment, and Biotechnology, 2015)

Bacillus amyloliquefaciens subsp. plantarum GR53, a potent biocontrol agent resists Rhizoctonia disease on Chinese cabbage through hormonal and antioxidants regulation - Sang-Mo Kang; Ramalingam Radhakrishnan; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2015)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Plant growth-promoting potential of endophytic fungi isolated from Solanum nigrum leaves - Abdur Rahim Khan; Ihsan Ullah; Muhammad Waqas; Raheem Shahzad; Sung-Jun Hong; Gun-Seok Park; Byung Kwon Jung; In-Jung Lee; Jae-Ho Shin (World Journal of Microbiology and Biotechnology, 2015)

Benzo(a)pyrene represses melanogenesis in B16F10 mouse melanoma cells - Da Hye Joo; Hwa Jun Cha; Karam Kim; Minhee Jung; Jung Min Ko; In Sook An; Sung Nae Lee; Hyun Hee Jang; Seunghee Bae; Nam Kyung Roh; Kyu Joong Ahn; Sungkwan An (Molecular & Cellular Toxicology, 2015)

Improvement in phytoremediation potential of Solanum nigrum under cadmium contamination through endophytic-assisted Serratia sp. RSC-14 inoculation - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Gun-Seok Park; Muhammad Waqas; Sung-Jun Hong; Byung Kwon Jung; Yunyoung Kwak; In-Jung Lee; Jae-Ho Shin (Environmental Science and Pollution Research, 2015)

Enterobacter sp. SE992-induced regulation of amino acids, sugars, and hormones in cucumber plants improves salt tolerance - Sang-Mo Kang; Ramalingam Radhakrishnan; Seok-Min Lee; Yeon-Gyeong Park; Ah-Yeong Kim; Chang-Woo Seo; In-Jung Lee (Acta Physiologiae Plantarum, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

IAA Producing Enterobacter sp. I-3 as a Potent Bio-herbicide Candidate for Weed Control: A Special Reference with Lettuce Growth Inhibition - Jae-Man Park; Ramalingam Radhakrishnan; Sang-Mo Kang; In-Jung Lee (Indian Journal of Microbiology, 2015)

Analysis of cytokine production in a newly developed canine tracheal epithelial cell line infected with H3N2 canine influenza virus - Woo-Jung Park; Byung-Joo Park; Young-Jo Song; Dong-Hun Lee; Seong-Su Yuk; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Archives of Virology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

Endophytic infection alleviates biotic stress in sunflower through regulation of defence hormones, antioxidants and functional amino acids - Muhammad Waqas; Abdul Latif Khan; Muhammad Hamayun; Raheem Shahzad; Yoon-Ha Kim; Kyung-Sook Choi; In-Jung Lee (European Journal of Plant Pathology, 2015)

Analysis of an ECG Record Database Reveals QT Interval Prolongation Potential of Famotidine in a Large Korean Population - Jaesuk Yun; Eun Hwangbo; Jongpill Lee; Chong-Run Chon; Peol A. Kim; In-Hye Jeong; Manyoung Park; Raewoong Park; Shin-Jung Kang; Donwoong Choi (Cardiovascular Toxicology, 2015)

Application of distributed KIneMatic wave STOrm Runoff Model (KIMSTORM) for flood simulation considering dam release in the NamHan river basin of Korea - In-Kyun Jung; Dong-Ryul Lee; Jong-Yoon Park; Geun-Ae Park; Seong-Joon Kim (Paddy and Water Environment, 2015)

Genetic characterization of porcine epidemic diarrhea virus in Korea from 1998 to 2013 - Seong-Hee Kim; Jung-Min Lee; Jongsun Jung; In-Joong Kim; Bang-Hun Hyun; Hyun-Il Kim; Choi-Kyu Park; Jae-Ku Oem; Yeon-Hee Kim; Myoung-Heon Lee; Kyoung-Ki Lee (Archives of Virology, 2015)

MicroRNA expression profiling of p-phenylenediamine treatment in human keratinocyte cell line - Hwa Jun Cha; Ok-Kyu Lee; Soo Yeon Kim; Jung-Min Ko; Su Young Kim; Ji Hye Son; Hyun Joo Han; Shunhua Li; Soo Young Kim; Kyu Joong Ahn; In-Sook An; Sungkwan An; et al. (Molecular & Cellular Toxicology, 2015)

Resilience of Penicillium resedanum LK6 and exogenous gibberellin in improving Capsicum annuum growth under abiotic stresses - Abdul Latif Khan; Muhammad Waqas; In-Jung Lee (Journal of Plant Research, 2015)

Seasonal variations and emission fluxes of monoterpene emitted from coniferous trees in East Asia: focused on Pinus rigida and Pinus koraiensis - Youn-Suk Son; Ki-Joon Kim; In-Ha Jung; Sung-Joo Lee; Jo-Chun Kim (Journal of Atmospheric Chemistry, 2015)

Production of transgenic spermatozoa by lentiviral transduction and transplantation of porcine spermatogonial stem cells - Byung-Gak Kim; Yong-Hee Kim; Yong-An Lee; Bang-Jin Kim; Ki-Jung Kim; Sang-Eun Jung; Hak-Jae Chung; Seongsoo Hwang; Sun-Ho Choi; Myung Jick Kim; Dong-Hoon Kim; In Cheul Kim; et al. (Tissue Engineering and Regenerative Medicine, 2014)

Phosphate Solubilizing Bacillus megaterium mj1212 Regulates Endogenous Plant Carbohydrates and Amino Acids Contents to Promote Mustard Plant Growth - Sang-Mo Kang; Ramalingam Radhakrishnan; Young-Hyun You; Gil-Jae Joo; In-Jung Lee; Ko-Eun Lee; Jin-Ho Kim (Indian Journal of Microbiology, 2014)

Isolation and characterization of 12 microsatellite loci from Maackia fauriei (Fabaceae), a large tree endemic to Jeju Island - In-Su Choi; Jung-Hyun Lee; Byoung-Hee Choi (Conservation Genetics Resources, 2014)

Genome-wide association analysis to identify SNP markers affecting teat numbers in an F2 intercross population between Landrace and Korean native pigs - Jae-Bong Lee; Eun-Ji Jung; Hee-Bok Park; Shil Jin; Dong-Won Seo; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee; Hyun-Tae Lim (Molecular Biology Reports, 2014)

Phytostabilization and Physicochemical Responses of Korean Ecotype Solanum nigrum L. to Cadmium Contamination - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Sung-Jun Hong; Muhammad Waqas; Gun-Seok Park; Yunyoung Kwak; JungBae Choi; Byung-Kwon Jung; Man Park; In-Jung Lee; Jae-Ho Shin (Water, Air, & Soil Pollution, 2014)

Phytohormone-producing fungal endophytes and hardwood-derived biochar interact to ameliorate heavy metal stress in soybeans - Muhammad Waqas; Abdul Latif Khan; Sang-Mo Kang; Yoon-Ha Kim; In-Jung Lee (Biology and Fertility of Soils, 2014)

Gordonibacter faecihominis sp. nov., isolated from human faeces - Jong-Sik Jin; Keun Chul Lee; In-Soon Park; Kwang Kyu Kim; Jong Seog Ahn; Yoshimi Benno; Masao Hattori; Jung-Sook Lee (Antonie van Leeuwenhoek, 2014)

Erratum to: Effects of different selenium levels on growth and regulation of laccase and versatile peroxidase in white-rot fungus, Pleurotus eryngii - Yong Hyun Kim; Hyoun-Su Lee; Hyun-Jung Kwon; Bharat Bhusan Patnaik; Kung-Woo Nam; Yeon Soo Han; In-Seok Bang; Man-Deuk Han (World Journal of Microbiology and Biotechnology, 2014)

Effects of different selenium levels on growth and regulation of laccase and versatile peroxidase in white-rot fungus, Pleurotus eryngii - Yong Hyun Kim; Hyoun-Su Lee; Hyun-Jung Kwon; Bharat Bhusan Patnaik; Kung-Woo Nam; Yeon Soo Han; In-Seok Bang; Man-Deuk Han (World Journal of Microbiology and Biotechnology, 2014)

Regulation of jasmonic acid biosynthesis by silicon application during physical injury to Oryza sativa L. - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Waqas; Hee-Jeong Jeong; Duk-Hwan Kim; Jeong Sheop Shin; Jong-Guk Kim; Myung-Hun Yeon; In-Jung Lee (Journal of Plant Research, 2014)

Silver nanoparticles induce apoptotic cell death in cultured cerebral cortical neurons - Sung-Hwan Kim; Je-Won Ko; Suk-Kyu Koh; In-Chul Lee; Jung-Mo Son; Changjong Moon; Sung-Ho Kim; Dong-Ho Shin; Jong-Choon Kim (Molecular & Cellular Toxicology, 2014)

Silicon Application to Rice Root Zone Influenced the Phytohormonal and Antioxidant Responses Under Salinity Stress - Yoon Ha Kim; Abdul Latif Khan; Muhammad Waqas; Jae Kyoung Shim; Duck Hwan Kim; Kyeong Yeoll Lee; In Jung Lee (Journal of Plant Growth Regulation, 2014)

Regulation of endogenous gibberellins and abscisic acid levels during different seed collection periods in Panax ginseng - Yoon-Ha Kim; In-Ok Ahn; Abdul Latif Khan; Muhammad Kamran; Muhammad Waqas; Joon-Soo Lee; Duk-Hwan Kim; Soo-Won Jang; In-Jung Lee (Horticulture, Environment, and Biotechnology, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Unveiling abundance and distribution of planktonic B acteria and A rchaea in a polynya in A mundsen S ea, A ntarctica - Jong‐Geol Kim; Soo‐Je Park; Zhe‐Xue Quan; Man‐Young Jung; In‐Tae Cha; So‐Jeong Kim; Kyoung‐Ho Kim; Eun‐Jin Yang; Young‐Nam Kim; Sang‐Hoon Lee; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary Polynyas, areas of open water surrounded by sea ice, are sites of intense primary production and ecological hotspots in the A ntarctic O cean. This study determined the spatial variation in communities of prokaryotes in a polynya in the A mundsen S ea using 454 pyrosequencing technology, and the results were compared with biotic and abiotic environmental factors. The bacterial abundance was correlated with that of phytoplankton, P haeocystis spp. and diatoms. A cluster analysis indicated that the bacterial communities in the surface waters of the polynya were distinct from those under the sea ice. Overall, two bacterial clades, P olaribacter (20–64%) and uncultivated O ceanospirillaceae (7–34%), dominated the surface water in the polynya while the P elagibacter clade was abundant at all depths (7–42%). The archaeal communities were not as diverse as the bacterial communities in the polynya, and marine group I was dominant (> 80%). Canonical correspondence analysis indicated that the oceanographic properties facilitated the development of distinct prokaryotic assemblages in the polynya. This analysis of the diversity and composition of the psychrophilic prokaryotes associated with high phytoplankton production provides new insights into the roles of prokaryotes in biogeochemical cycles in high‐latitude polynyas.

Expression of gibberellin 2-oxidase 4 from Arabidopsis under the control of a senescence-associated promoter results in a dominant semi-dwarf plant with normal flowering - Dong Hee Lee; In Chul Lee; Kook Jin Kim; Dong Su Kim; Hyung Jin Na; In-Jung Lee; Sang-Mo Kang; Hyung-Woo Jeon; Phi Yen Le; Jae-Heung Ko (Journal of Plant Biology, 2014)

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Parental effects on nutritional and antioxidants constituents in seeds of peanut cv. Boreom 1 - Ramalingam Radhakrishnan; Suk-Bok Pae; Sang-Mo Kang; In-Jung Lee; In-Youl Baek (Journal of Crop Science and Biotechnology, 2014)

Effects of strobe light stimulation on postnatal developing rat retina - Jung-a Shin; Eojin Jeong; In-Beom Kim; Hwa-young Lee (Experimental Brain Research, 2014)

Fungal endophyte Penicillium janthinellum LK5 can reduce cadmium toxicity in Solanum lycopersicum (Sitiens and Rhe) - Abdul Latif Khan; Muhammad Waqas; Javid Hussain; Ahmed Al-Harrasi; In-Jung Lee (Biology and Fertility of Soils, 2014)

Enhanced regeneration of rabbit mandibular defects through a combined treatment of electrical stimulation and rhBMP-2 application - Junghoon Kim; Hoon Joo Yang; Tae Hyung Cho; Sung Eun Lee; Yong Doo Park; Hyun Man Kim; In Sook Kim; Young-kwon Seo; Soon Jung Hwang; Sung June Kim (Medical & Biological Engineering & Computing, 2013)

Comparative genetic diversity of wild and hatchery-produced Pacific oyster (Crassostrea gigas) populations in Korea using multiplex PCR assays with nine polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Woo Jin Kim; Hyun Jeong Lim; Eun Mi Kim; Soon Gyu Byun; Young Baek Hur; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Genetic differences between wild and hatchery populations of red sea cucumber (Stichopus japonicus) inferred from microsatellite markers: implications for production and stocking programs design - Hye Suck An; Jang Wook Lee; Seong Wan Hong; Ha Neui Hong; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Combined effects of an antioxidant and caspase inhibitor on the reversal of hepatic fibrosis in rats - Do Young Kim; Sook In Chung; Simon Weonsang Ro; Yong Han Paik; Jung Il Lee; Man Kil Jung; Min Goo Lee; Young Nyun Park; Kwan Sik Lee; Jung Gyu Park; Hee Dong Park; Kwang-Hyub Han (Apoptosis, 2013)

Regulation of salicylic acid, jasmonic acid and fatty acids in cucumber (Cucumis sativus L.) by spermidine promotes plant growth against salt stress - Ramalingam Radhakrishnan; In-Jung Lee (Acta Physiologiae Plantarum, 2013)

Fungal endophyte Penicillium janthinellum LK5 improves growth of ABA-deficient tomato under salinity - Abdul Latif Khan; Muhammad Waqas; Abdur Rahim Khan; Javid Hussain; Sang-Mo Kang; Syed Abdullah Gilani; Muhammad Hamayun; Jae-Ho Shin; Muhammad Kamran; Ahmed Al-Harrasi; Byung-Wook Yun; Muhammad Adnan; et al. (World Journal of Microbiology and Biotechnology, 2013)

Identification of a drought-induced rice gene, OsSAP, that suppresses Bax-induced cell death in yeast - Mohammad Ubaidillah; Kyung-A Kim; Yoon Ha Kim; In-Jung Lee; Byung-Wook Yun; Doh Hoon Kim; Gary J. Loake; Kyung-Min Kim (Molecular Biology Reports, 2013)

Dietary aflatoxin B1 intake, genetic polymorphisms of CYP1A2, CYP2E1, EPHX1, GSTM1, and GSTT1, and gastric cancer risk in Korean - Sang-Yong Eom; Dong-Hyuk Yim; Yanwei Zhang; Jung-Kuk Yun; Sun In Moon; Hyo-Yung Yun; Young-Jin Song; Sei-Jin Youn; Taisun Hyun; Joo-Seung Park; Byung Sik Kim; Jong-Young Lee; et al. (Cancer Causes & Control, 2013)

Treadmill exercise represses neuronal cell death and inflammation during Aβ-induced ER stress by regulating unfolded protein response in aged presenilin 2 mutant mice - Eun-Bum Kang; In-Su Kwon; Jung-Hoon Koo; Eung-Joon Kim; Chul-Hyun Kim; Jin Lee; Choon-Ho Yang; Young-Il Lee; In-Ho Cho; Joon-Yong Cho (Apoptosis, 2013)

Natronomonas gomsonensis sp. nov., isolated from a solar saltern - Tae-Yoon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Man-Young Jung; Sang-A Lee; Seong Woon Roh; Kyung June Yim; Takashi Itoh; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Removal torque analysis of chemically modified hydrophilic and anodically oxidized titanium implants with constant angular velocity for early bone response in rabbit tibia - Hyo-Jung Lee; In-Sung Yeo; Taek-Ka Kwon (Tissue Engineering and Regenerative Medicine, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

Overexpression of a Brassica rapa MADS-box gene, BrAGL20, induces early flowering time phenotypes in Brassica napus - Joon Ki Hong; Soo-Yun Kim; Kwang-Soo Kim; Soo-Jin Kwon; Jung Sun Kim; Jin A. Kim; Soo In Lee; Yeon-Hee Lee (Plant Biotechnology Reports, 2013)

Erratum to: Regulation of arterial blood pressure by Akt1-dependent vascular relaxation - Jung Min Ha; Young Whan Kim; Dong Hyung Lee; Sung Ji Yun; Eun Kyoung Kim; In Hye Jin; Ji Hyun Kim; Chi Dae Kim; Hwa Kyoung Shin; Sun Sik Bae (Journal of Molecular Medicine, 2013)

Spermine Promotes Acclimation to Osmotic Stress by Modifying Antioxidant, Abscisic Acid, and Jasmonic Acid Signals in Soybean - Ramalingam Radhakrishnan; In-Jung Lee (Journal of Plant Growth Regulation, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Antisense-overexpression of the MsCOMT gene induces changes in lignin and total phenol contents in transgenic tobacco plants - Eun Soo Seong; Ji Hye Yoo; Jae Geun Lee; Hee Young Kim; In Seong Hwang; Kweon Heo; Jae Kwang Kim; Jung Dae Lim; Erik J. Sacks; Chang Yeon Yu (Molecular Biology Reports, 2013)

Sequence polymorphisms in ribosomal RNA genes and variations in chromosomal loci of Oenothera odorata and O. laciniata - Jun Hyung Seo; Hyo Geun Bae; Da Hee Park; Beom Seok Kim; Jong Wook Lee; Jung In Lee; Dong Hyun Kim; Seok Won Lee; Bong Bo Seo (Genes & Genomics, 2013)

Ameliorative effects of spermine against osmotic stress through antioxidants and abscisic acid changes in soybean pods and seeds - Ramalingam Radhakrishnan; In-Jung Lee (Acta Physiologiae Plantarum, 2013)

Volumetric Analysis of Cerebellum in Short-Track Speed Skating Players - In Sung Park; Nam Joon Lee; Tae-Young Kim; Jin-Hoon Park; Yu-Mi Won; Yong-Ju Jung; Jin-Hwan Yoon; Im Joo Rhyu (The Cerebellum, 2012)

Effect of proton beam irradiation on germination, seedling growth, and pasting properties of starch in rice - Sang-Kuk Kim; Shin-Young Park; Kye-Ryung Kim; Jong-Hee Shin; Su-Yong Kim; Hak-Yoon Kim; In-Jung Lee (Journal of Crop Science and Biotechnology, 2012)

Gene expression profiles of human lung epithelial cells exposed to toluene - Yu-Ri Kim; In-Kyoung Kim; Seung Ho Lee; Eun-Jung Lee; Mi Jung Pyo; Hee Ra Lee; Jong Pil Youn; MoonJu Oh; Seung Yong Hwang; Meyoung-Kon Kim (Toxicology and Environmental Health Sciences, 2012)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

Effects of elevated carbon dioxide and temperature on photosynthesis and fruit characteristics of ‘Niitaka’ pear (Pyrus pyrifolia Nakai) - Jeom-Haw Han; Jung Gun Cho; In-Chang Son; Seung Heui Kim; In-Bog Lee; In Myung Choi; Daeil Kim (Horticulture, Environment, and Biotechnology, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

Sequence polymorphisms of Der f 1, Der p 1, Der f 2 and Der p 2 from Korean house dust mite isolates - Kyoung Yong Jeong; In-Yong Lee; Tai-Soon Yong; Jae-Hyun Lee; Eun-Jin Kim; Joo-Shil Lee; Chein-Soo Hong; Jung-Won Park (Experimental and Applied Acarology, 2012)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Influence of genotype, explant source, and gelling agent on in vitro shoot regeneration of chrysanthemum - Ki-Byung Lim; Soo Jin Kwon; Soo In Lee; Yoon-Jung Hwang; Aung Htay Naing (Horticulture, Environment, and Biotechnology, 2012)

Overexpression of Brassica rapa SHI-RELATED SEQUENCE genes suppresses growth and development in Arabidopsis thaliana - Joon Ki Hong; Jin A. Kim; Jung Sun Kim; Soo In Lee; Bon Sung Koo; Yeon-Hee Lee (Biotechnology Letters, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Characterization of phenotypic variants of Clavibacter michiganensis subsp. michiganensis isolated from Capsicum annuum - Kyu-Ock Yim; Hyok-In Lee; Jung-Hee Kim; Seung-Don Lee; Jung-Hee Cho; Jae-Soon Cha (European Journal of Plant Pathology, 2012)

Exophiala sp.LHL08 association gives heat stress tolerance by avoiding oxidative damage to cucumber plants - Abdul Latif Khan; Muhammad Hamayun; Muhammad Waqas; Sang-Mo Kang; Yoon-Ha Kim; Duk-Hwan Kim; In-Jung Lee (Biology and Fertility of Soils, 2012)

OsREL2, a rice TOPLESS homolog functions in axillary meristem development in rice inflorescence - Yerim Kwon; Si-in Yu; Joo-hyuk Park; Ying Li; Jin-Hee Han; Hemasundar Alavilli; Jung-Il Cho; Tae-Houn Kim; Jong-Seong Jeon; Byeong-ha Lee (Plant Biotechnology Reports, 2012)

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients - In-Wha Kim; Yoo Jin Moon; Eunhee Ji; Kyung Im Kim; Nayoung Han; Sung Ju Kim; Wan Gyoon Shin; Jongwon Ha; Jeong-Hyun Yoon; Hye Suk Lee; Jung Mi Oh (European Journal of Clinical Pharmacology, 2012)

Identification and characterization of stress resistance related genes of Brassica rapa - Nasar Uddin Ahmed; Jong-In Park; Hee-Jeong Jung; Mi-Suk Seo; Thamilarasan Senthil Kumar; In-Ho Lee; Ill-Sup Nou (Biotechnology Letters, 2012)

Occurrence of bacterial rot of onion caused by Bacillus amyloliquefaciens in Korea - Sun-Kyoung Hwang; Chang-Gi Back; Nang Kyu Kyu Win; Myung Kyum Kim; Hee-Dae Kim; In-Kyu Kang; Sang-Chul Lee; Hee-Young Jung (Journal of General Plant Pathology, 2012)

Pure culture of Metarhizium anisopliae LHL07 reprograms soybean to higher growth and mitigates salt stress - Abdul Latif Khan; Muhammad Hamayun; Sumera Afzal Khan; Sang-Mo Kang; Zabta Khan Shinwari; Muhammad Kamran; Shafiq ur Rehman; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2012)

Determination of endocrine disrupting chemicals in water samples by dispersive liquid–liquid microextraction combined with liquid chromatography–fluorescence detection - Yeonsuk Ryu; Jung-In Lee; Jae-Won Moon; Jung-Hyun Kim; Ji-Hwan Park; Su-Yeon Park; Young A. Yoon; Jeongmi Lee (Journal of Pharmaceutical Investigation, 2012)

Gene expression analysis identifies DNA damage-related markers of benzo[a]pyrene exposure in HepG2 human hepatocytes - Mi-Kyung Song; Ji-Seong Yoon; Mee Song; Han-Seam Choi; Chan-Young Shin; Youn-Jung Kim; Woo-In Ryu; Hyo-Sun Lee; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

CYP2C9*3 and *13 alleles significantly affect the pharmacokinetics of irbesartan in healthy Korean subjects - Chang-Ik Choi; Mi-Jeong Kim; Eun-Kyung Chung; Hye-In Lee; Choon-Gon Jang; Jung-Woo Bae; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2012)

Mutualistic association of Paecilomyces formosus LHL10 offers thermotolerance to Cucumis sativus - Abdul Latif Khan; Muhammad Hamayun; Ramalingam Radhakrishnan; Muhammad Waqas; Sang-Mo Kang; Yoon-Ha Kim; Jae-Ho Shin; Yeon-Sik Choo; Jong-Guk Kim; In-Jung Lee (Antonie van Leeuwenhoek, 2012)

Regulation of arterial blood pressure by Akt1-dependent vascular relaxation - Jung Min Ha; Young Whan Kim; Dong Hyung Lee; Sung Ji Yun; Eun Kyoung Kim; In Hye Jin; Ji Hyun Kim; Chi Dae Kim; Hwa Kyoung Shin; Sun Sik Bae (Journal of Molecular Medicine, 2011)

Developmental expression of plasma glutathione peroxidase during mouse organogenesis - Ki Youn Jung; In-Jeoung Baek; Jung-Min Yon; Se-Ra Lee; Mi-Ra Kim; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2011)

QTL analysis of fruit length using rRAMP, WRKY, and AFLP markers in chili pepper - Heung-Ryul Lee; Ki-Taek Kim; Hyoun-Joung Kim; Jung-Heon Han; Jeong-Ho Kim; Seon-In Yeom; Hyun Jung Kim; Won-Hee Kang; Jinxia-Shi; Soung-Woo Park; Ik-Hyun Bae; Semin Lee; et al. (Horticulture, Environment, and Biotechnology, 2011)

Influence of Short-Term Silicon Application on Endogenous Physiohormonal Levels of Oryza sativa L. Under Wounding Stress - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Hamayun; Sang Mo Kang; Yoon Jung Beom; In-Jung Lee (Biological Trace Element Research, 2011)

Higher DNA repair activity is related with longer replicative life span in mammalian embryonic fibroblast cells - Seong-Hoon Park; Hong-Jun Kang; Hyun-Seok Kim; Min-Ju Kim; Jee-In Heo; Jeong-Hyeon Kim; Yoon-Jung Kho; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Biogerontology, 2011)

Temperature trends in the skin/surface, mid-troposphere and low stratosphere near Korea from satellite and ground measurements - Jung-Moon Yoo; Young-In Won; Young-Jun Cho; Myeong-Jae Jeong; Dong-Bin Shin; Suk-Jo Lee; Yu-Ri Lee; Soo-Min Oh; Soo-Jin Ban (Asia-Pacific Journal of Atmospheric Sciences, 2011)

The use of healthy volunteers instead of patients to inform drug dosing studies: a [11C]raclopride PET study - Euitae Kim; Oliver D. Howes; Bo-Hyung Kim; Kyung-Sang Yu; Jae Min Jeong; Jae Sung Lee; Su Jin Kim; In-Jin Jang; Jung Shin Park; Yong Gil Kim; Sang-Goo Shin; Federico E. Turkheimer; et al. (Psychopharmacology, 2011)

Isolation of an Rx homolog from C. annuum and the evolution of Rx genes in the Solanaceae family - Jinxia Shi; Seon-In Yeom; Won-Hee Kang; Min-Kyu Park; Doil Choi; Jin-Kyung Kwon; Jung-Heon Han; Heung-Ryul Lee; Byung-Dong Kim; Byoung-Cheorl Kang (Plant Biotechnology Reports, 2011)

Phospholipid hydroperoxide glutathione peroxidase gene is regulated via an estrogen and estrogen receptor signaling in cultured mouse fetuses - In-Jeoung Baek; Ki Youn Jung; Jung-Min Yon; Se-Ra Lee; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (In Vitro Cellular & Developmental Biology - Animal, 2011)

A grid-based rainfall-runoff model for flood simulation including paddy fields - In-Kyun Jung; Jong-Yoon Park; Geun-Ae Park; Mi-Seon Lee; Seong-Joon Kim (Paddy and Water Environment, 2011)

Natural 15N abundance of paddy rice (Oryza sativa L.) grown with synthetic fertilizer, livestock manure compost, and hairy vetch - Soek-In Yun; Sang-Sun Lim; Gwang-Sung Lee; Sang-Mo Lee; Han-Yong Kim; Hee-Myong Ro; Woo-Jung Choi (Biology and Fertility of Soils, 2011)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Isolation and characterization of 28 polymorphic SSR loci from castor bean (Ricinus communis L.) - Kyoung-In Seo; Gi-An Lee; Kyung-Ho Ma; Do-Yoon Hyun; Yong-Jin Park; Jong-Wook Jung; Sok-Young Lee; Jae-Gyun Gwag; Chung-Kon Kim; Myung-Chul Lee (Journal of Crop Science and Biotechnology, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Importance of region-specific epithelial rearrangements in mouse rugae development - Wern-Joo Sohn; Hitoshi Yamamoto; Hong-In Shin; Zae Young Ryoo; Sanggyu Lee; Yong-Chul Bae; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Molecular characterization of rotavirus diarrhea among children in South Korea: detection of an unusual G11 strain - Jung Ok Shim; In Hyuk Baek; Van Phan Le; Eun-Mi Ko; Won-Seok Seok; Young Uh; Ja Kyoung Kim; Sung Yeon Ahn; Hyeon Soo Lee; Eell Ryoo; So-Yeon Shim; Wonkeun Song; et al. (Archives of Virology, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

Characterization of chemical properties of atmospheric aerosols over Anmyeon (South Korea), a super site under Global Atmosphere Watch - Sung-Hwa Park; A. S. Panicker; Dong-In Lee; Woon-Seon Jung; Sang-Min Jang; Min Jang; Dongchul Kim; Yu-Won Kim; Harrison Jeong (Journal of Atmospheric Chemistry, 2010)

Isolation and characterization of a Glutamate decarboxylase (GAD) gene and their differential expression in response to abiotic stresses from Panax ginseng C. A. Meyer - Jung-Hye Lee; Yu-Jin Kim; Dae-Young Jeong; Gayathri Sathiyaraj; Rama Krishna Pulla; Ju-Sun Shim; Jun-Gyo In; Deok-Chun Yang (Molecular Biology Reports, 2010)

Determining hypocentral parameters for local earthquakes under ill conditions using genetic algorithm - Woohan Kim; In-Kyeong Hahm; Won-Young Kim; Jung Mo Lee (Journal of Seismology, 2010)

Increase of isoflavones in soybean callus by Agrobacterium-mediated transformation - Nan Jiang; Eun-Hee Jeon; Jung-Hun Pak; Tae-Joung Ha; In-Youl Baek; Woo-Suk Jung; Jai-Heon Lee; Doh-Hoon Kim; Hong-Kyu Choi; Zheng Cui; Young-Soo Chung (Plant Biotechnology Reports, 2010)

Mutation in Wilted Dwarf and Lethal 1 (WDL1) causes abnormal cuticle formation and rapid water loss in rice - Jong-Jin Park; Ping Jin; Jinmi Yoon; Jung-Il Yang; Hee Joong Jeong; Kosala Ranathunge; Lukas Schreiber; Rochus Franke; In-Jung Lee; Gynheung An (Plant Molecular Biology, 2010)

Evaluation of the toxicological properties and hepatoprotective effects of PAI-N002, a mixture of herbal extracts, in rats - Sung-Hwan Kim; Jeong-Hyeon Lim; In-Sik Shin; Changjong Moon; Soo-Hyun Park; Sung-Ho Kim; Jung-Sik Lee; Eun-Hye Kwon; Jong-Choon Kim (Molecular & Cellular Toxicology, 2010)

Antitumor activity of methylan polysaccharide derivatives - Priyadharshini Ramachandran; Marimuthu Jeya; Hee-Jung Moon; Kyoung-Mi Lee; In-Won Kim; Jung-Hoe Kim; Jung-Kul Lee (Biotechnology Letters, 2010)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Overexpression and Inactivation of UGT73B2 Modulate Tolerance to Oxidative Stress in Arabidopsis - In A Kim; Jung-Ok Heo; Kwang Suk Chang; Shin Ae Lee; Mi-Hyun Lee; Chae Eun Lim; Jun Lim (Journal of Plant Biology, 2010)

Growth promotion of cucumber by pure cultures of gibberellin-producing Phoma sp. GAH7 - Muhammad Hamayun; Sumera Afzal Khan; Abdul Latif Khan; Dong-Sheng Tang; Javid Hussain; Bashir Ahmad; Yasir Anwar; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2010)

Bifidobacterium longum HY8004 attenuates TNBS-induced colitis by inhibiting lipid peroxidation in mice - In-Ah Lee; Eun-Ah Bae; Jung-Hee Lee; Hoyong Lee; Young-Tae Ahn; Chul-Sung Huh; Dong-Hyun Kim (Inflammation Research, 2010)

Effect of combined indole acetic acid and mepiquat chloride on endogenous gibberellins and tuber growth in Chinese yam (Dioscorea opposita Thunb.) - Sang Kuk Kim; Hong Jib Choi; In Jung Lee; Hak Yoon Kim (Journal of Crop Science and Biotechnology, 2010)

Comparative study of the chemical composition and antioxidant activity of six essential oils and their components - Seun-Ah Yang; Sang-Kyung Jeon; Eun-Jung Lee; Chang-Hyun Shim; In-Seon Lee (Natural Product Research, 2010)

Identification of a null allele of cytochrome P450 3A7: CYP3A7 polymorphism in a Korean population - Sang Seop Lee; Hyun-Ju Jung; Jung Soon Park; In-June Cha; Doo-Yeoun Cho; Jae-Gook Shin (Molecular Biology Reports, 2010)

Effects of the number of events, their depth distributions, and the number of layers in a model on traveltime inversion - Woohan Kim; In-Kyung Hahm; Jung Mo Lee (Geosciences Journal, 2009)

Gibberellin production by pure cultures of a new strain of Aspergillus fumigatus - Muhammad Hamayun; Sumera Afzal Khan; Mir Ajab Khan; Abdul Latif Khan; Sang-Mo Kang; Sang-Kuk Kim; Gil-Jae Joo; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Effect of light on endogenous levels of gibberellin and abscisic acid in seed germination of photoblastic weedy rice (Oryza sativa L.) - Sang-Yeol Kim; Sun-Joo Hwang; In-Jung Lee; Dong-Hyun Shin; Sung-Tae Park; Un-Sang Yeo; Hang-Won Kang (Journal of Crop Science and Biotechnology, 2009)

Analysis of the helicase gene of Korean swine hepatitis E virus isolates and trends in viral infection - Won-Jung Lee; Mi Lan Kang; Seung-Bin Cha; Bong-Kyun Park; In-Soo Choi; Han Sang Yoo (Archives of Virology, 2009)

Isolation of S-adenosyl-L-methionine synthetase gene from Panax ginseng C.A. meyer and analysis of its response to abiotic stresses - Rama Krishna Pulla; Yu-Jin Kim; Shohana Parvin; Ju-Sun Shim; Jung-Hye Lee; Yeon-Ju Kim; Jun-Gyo In; Kalai Selvi Senthil; Deok-Chun Yang (Physiology and Molecular Biology of Plants, 2009)

Methyl jasmonate alleviated salinity stress in soybean - Ji Young Yoon; Muhammad Hamayun; Su-Kyung Lee; In-Jung Lee (Journal of Crop Science and Biotechnology, 2009)

Gibberellin production and plant growth promotion by a newly isolated strain of Gliomastix murorum - Sumera Afzal Khan; Muhammad Hamayun; Ho-Youn Kim; Hyeok-Jun Yoon; In-Jung Lee; Jong-Guk Kim (World Journal of Microbiology and Biotechnology, 2009)

Cladosporium sphaerospermum as a new plant growth-promoting endophyte from the roots of Glycine max (L.) Merr. - Muhammad Hamayun; Sumera Afzal Khan; Nadeem Ahmad; Dong-Sheng Tang; Sang-Mo Kang; Chae-In Na; Eun-Young Sohn; Young-Hyun Hwang; Dong-Hyun Shin; Byung-Hyun Lee; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Enhanced fungal resistance in Arabidopsis expressing wild rice PR-3 (OgChitIVa) encoding chitinase class IV - Jung-Hun Pak; Eun-Sook Chung; Sang-Hyun Shin; Eun-Hee Jeon; Mi-Jin Kim; Hye-Young Lee; Ji-Ung Jeung; Nam-In Hyung; Jai-Heon Lee; Young-Soo Chung (Plant Biotechnology Reports, 2009)

Quantification of endogenous gibberellins in two flax (Linum usitatissimum L.) cultivars during seed development - Sang-Kuk Kim; Eun-Young Sohn; Sang-Mo Kang; In-Jung Lee (Journal of Crop Science and Biotechnology, 2009)

Starch properties of native foxtail millet, Setaria italica Beauv. - Sang-Kuk Kim; Eun-Young Sohn; In-Jung Lee (Journal of Crop Science and Biotechnology, 2009)

Clostridium difficile toxin A promotes dendritic cell maturation and chemokine CXCL2 expression through p38, IKK, and the NF-κB signaling pathway - Jin Young Lee; Hyunah Kim; Mi Yeon Cha; Hong Gyu Park; Young-Jeon Kim; In Young Kim; Jung Mogg Kim (Journal of Molecular Medicine, 2009)

A new strain of Arthrinium phaeospermum isolated from Carex kobomugi Ohwi is capable of gibberellin production - Sumera Afzal Khan; Muhammad Hamayun; Ho-youn Kim; Hyeok-jun Yoon; Jong-cheol Seo; Yeon-sik Choo; In-jung Lee; Sang-dal Kim; In-koo Rhee; Jong-guk Kim (Biotechnology Letters, 2009)

Gibberellin production and phosphate solubilization by newly isolated strain of Acinetobacter calcoaceticus and its effect on plant growth - Sang-Mo Kang; Gil-Jae Joo; Muhammad Hamayun; Chae-In Na; Dong-Hyun Shin; Hak Youn Kim; Jin-Kyu Hong; In-Jung Lee (Biotechnology Letters, 2009)

Arsenic reduction and precipitation by shewanella sp.: Batch and column tests - Mi-Sun Lim; In Wook Yeo; Yul Roh; Kang-Kun Lee; Myung Chae Jung (Geosciences Journal, 2008)

The spatio-temporal expression pattern of cytoplasmic Cu/Zn superoxide dismutase (SOD1) mRNA during mouse embryogenesis - Jung-Min Yon; In-Jeoung Baek; Se-Ra Lee; Yan Jin; Mi-Ra Kim; Sang-Seop Nahm; Jong-Soo Kim; Byeongwoo Ahn; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2008)

Prevalence and molecular characterization of meq in feather follicular epithelial cells of Korean broiler chickens - Jung-Won Kang; Sun-Hee Cho; In-Pil Mo; Dong-Woo Lee; Hyuk-Joon Kwon (Virus Genes, 2007)

Superoxide anion regulates plant growth and tuber development of potato - Mi-Sun Kim; Hyun-Soon Kim; Yoon-Shik Kim; Kwang-Hyun Baek; Hyun-Woo Oh; Kyu-Woong Hahn; Ro-Na Bae; In-Jung Lee; Hyouk Joung; Jae-Heung Jeon (Plant Cell Reports, 2007)

Tissue expression and cellular localization of phospholipid hydroperoxide glutathione peroxidase (PHGPx) mRNA in male mice - In-Jeoung Baek; Dong-Suk Seo; Jung-Min Yon; Se-Ra Lee; Yan Jin; Sang Soep Nahm; Jae-Hwang Jeong; Young-Kug Choo; Jong-Koo Kang; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2007)

Determination of hypocentral parameters of local earthquakes using weighting factor based on take-off angle - In Kyeong Hahm; Woohan Kim; Jung Mo Lee; Jeong Soo Jeon (Geosciences Journal, 2007)

Ca2+ and Cu2+ supplementation increases mannitol production by Candida magnoliae - Jung-Kul Lee; Deok-Kun Oh; Hee-Yeol Song; In-Won Kim (Biotechnology Letters, 2007)

ENA Actimineral Resource A restores bone loss and bone quality in ovariectomized rats - Sun Hee Do; Sung-Yong Hwa; Won-Il Jeong; Ji-Won Lee; Hyun-Jung Kim; In-Seon Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Apoglossum minimum and A. gregarium (Delesseriaceae, Rhodophyta),Two New Records from Korea - Mi-Ra Park; Jung-Hyun Oak; In-Kyu Lee (Algae, 2006)

A rice dehydration-inducible SNF1-related protein kinase 2 phosphorylates an abscisic acid responsive element-binding factor and associates with ABA signaling - Min-Ju Chae; Jung-Sook Lee; Myung-Hee Nam; Kun Cho; Ji-Yeon Hong; Sang-A Yi; Seok-Cheol Suh; In-Sun Yoon (Plant Molecular Biology, 2006)

Reproducibility of Quantitative Estimate of Magnetocardiographic Ventricular Depolarization and Repolarization Parameters in Healthy Subjects and Patients with Coronary Artery Disease - Hyun Kyoon Lim; Namsik Chung; Kiwoong Kim; Young-Guk Ko; Hyukchan Kwon; Yong-Ho Lee; Jin-Bae Kim; Jung Rae Cho; Jin-Mok Kim; In-Seon Kim; Yong Ki Park (Annals of Biomedical Engineering, 2006)

Fruit ripening-related expression of a gene encoding group 5 late embryogenesis abundant protein inCitrus - Oh-Sung Jeon; Chan-Shick Kim; Sam-Pin Lee; Sung Ku Kang; Chang-Myung Kim; Bong-Gyoon Kang; Yoonkang Hur; In-Jung Kim (Journal of Plant Biology, 2006)

Gamma radiation and hormone treatment as tools to reduce salt stress in rice (Oryza sativa L.) - Myung-Hwa Baek; Byung Yeoup Chung; Jin-Hong Kim; Seung Gon Wi; Jae-Sung Kim; In-Jung Lee (Journal of Plant Biology, 2006)

In vitro and in planta Interaction Evidence between Nicotiana tabacum Thaumatin-Like Protein 1 (TLP1) and Cucumber mosaic virus Proteins - Min Jung Kim; Byung-Kook Ham; Hwa Ran Kim; In-Ju Lee; Young Jin Kim; Ki Hyun Ryu; Young In Park; Kyung-Hee Paek (Plant Molecular Biology, 2005)

Gene expression of the biosynthetic enzymes and biosynthesis of starch during Rice Grain development - Jung-Won Hwang; Sung-Kon Kim; Jeom-Sig Lee; In-Soo Kim (Journal of Plant Biology, 2005)

Brain-derived neurotrophic factor modulates the dopaminergic network in the rat retina after axotomy - Eun-Jin Lee; Myoung-Chul Song; Hyun-Ju Kim; Eun-Jin Lim; In-Beom Kim; Su-Ja Oh; Jung-IL Moon; Myung-Hoon Chun (Cell and Tissue Research, 2005)

Fractal Stochastic Modeling of Spiking Activity in Suprachiasmatic Nucleus Neurons - Sung-IL Kim; Jaeseung Jeong; Yongho Kwak; Yang In Kim; Seung Hun Jung; Kyoung J. Lee (Journal of Computational Neuroscience, 2005)

Taxonomy of the Genus Sargassum (Fucales, Phaeophyceae) from Korea I. Subgenus Bactrophycus Section Teretia - Jung-Hyun Oak; In-Kyu Lee (Algae, 2005)

Taxonomic Reappraisal of Sphacelaria rigidula and S. fusca (Sphacelariales, Phaeophyceae) Based on Morphology and Molecular Data with Special Reference to S. didichotoma - Yeon-Shim Keum; Jung-Hyun Oak; Stefano G.A. Draisma; Willem F. Prud'homme van Reine; In-Kyu Lee (Algae, 2005)

Genotyping Possible Polymorphic Variants of Human Mismatch Repair Genes in Healthy Korean Individuals and Sporadic Colorectal Cancer Patients - Jin C. Kim; Seon A. Roh; Kum H. Koo; In H. Ka; Hee C. Kim; Chang S. Yu; Kang H. Lee; Jung S. Kim; Han I. Lee; Walter F. Bodmer (Familial Cancer, 2004)

Growth promotion of red pepper plug seedlings and the production of gibberellins by Bacillus cereus, Bacillus macroides and Bacillus pumilus - Gil-Jae Joo; Young-Mog Kim; In-Jung Lee; Kyung-Sik Song; In-Koo Rhee (Biotechnology Letters, 2004)

Isolation and characterization of a novel rice Ca2 +-regulated protein kinase gene involved in responses to diverse signals including cold, light, cytokinins, sugars and salts - Kyung-Nam Kim; Jung-Sook Lee; Hee Han; Seung Ah Choi; Seung Joo Go; In Sun Yoon (Plant Molecular Biology, 2003)

Taxonomy of Hypoglossum (Delesseriaceae, Rhodophyta) from Korea - Jung-Hyun Oak; Mi-Ra Park; In-Kyu Lee (Algae, 2002)

Synthesis of kyotorphin precursor from eutectic mixtures catalysed by α-chymotrypsin - Chulyoung Kim; In Kyu Lee; Jung Eun Ahn; Chul Soo Shin (Biotechnology Letters, 2001)

Optimization of uracil addition for curdlan (β-1→3-glucan) production by Agrobacterium sp. - Jung-heon Lee; In Young Lee (Biotechnology Letters, 2001)

Morphological analysis of CD15-immunoreactive neurons in the guinea pig retina - In-Beom Kim; Eun-Jin Lee; Jung-Il Moon; Myung-Hoon Chun (Cell and Tissue Research, 2001)

Curdlan gels as protein drug delivery vehicles - Beom Soo Kim; In Duck Jung; Jong Sik Kim; Jung-heon Lee; In Young Lee; Kyung Bok Lee (Biotechnology Letters, 2000)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)

Enhanced production of laccase in Trametes vesicolor by the addition of ethanol - In-Young Lee; Kyung-Hee Jung; Choong-Hwan Lee; Young-Hoon Park (Biotechnology Letters, 1999)

Identification of MADS genes from a brown alga,Sargassum fulvellum - Jongmin Nam; Yoo Kyung Lee; Jung Hyun Oak; Gynheung An; In Kyu Lee (Journal of Plant Biology, 1999)